Adhesive film and method for producing adhesive film
By using a photocured glue layer and using light irradiation at a wavelength of 405nm and an optical density of 80mW/cm², a glue layer with high anchoring force and high thermal impedance is formed, which solves the problem of insufficient thermal impedance and handling of electronic components in the high temperature environment in the prior art, and achieves the effect of not being easy to peel off at high temperatures.
Patent Information
- Application Number
- JP2024159177
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-09-13
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to provide high thermal impedance and good handling of electronic components in high temperature environments, and the anchoring force of the conventional hard adhesive layer on the substrate is insufficient, resulting in easy peeling at high temperatures.
An ultra-high pressure mercury light-curing adhesive layer with light curing characteristics is used to form a glue layer with high anchoring force and high thermal impedance through light irradiation at a wavelength of 405nm and an optical density of 80mW/cm².
It realizes high thermal impedance and good handling of electronic components in high temperature environments, and is not easy to peel off at high temperatures, improving the processing and use stability of electronic components.
Smart Images

Figure 2025043333000001 
Figure 2025043333000002 
Figure 2025043333000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive film and a method for producing the adhesive film. [Background technology]
[0002] Conventionally, adhesive tapes and adhesive films are used to fix components in electronic devices. For example, adhesive tapes and adhesive films are used to adhere a cover panel for protecting the surface of a portable electronic device to a touch panel module or a display panel module, or to adhere a touch panel module to a display panel module. Such adhesive tapes and adhesive films used to fix electronic device components have an adhesive layer containing an adhesive composition, and in addition to high adhesion, functions such as heat resistance, thermal conductivity, and impact resistance are required depending on the environment of the site where they are used (for example, Patent Documents 1 to 3).
[0003] During processing of electronic components such as semiconductors, in order to facilitate the handling of the electronic components and prevent them from being damaged, the electronic components are fixed to a support plate via a temporary fixing material made of a pressure-sensitive adhesive composition, or an adhesive film having an adhesive layer is attached to the electronic components to protect them. For example, when a thick-film wafer cut from a high-purity silicon single crystal or the like is ground to a predetermined thickness to obtain a thin-film wafer, the thick-film wafer is adhered to a support plate via a pressure-sensitive adhesive composition.
[0004] Thus, pressure-sensitive adhesive compositions and adhesive films used for electronic components are required to have high enough adhesion to firmly fix the electronic components during processing, and also to be able to be peeled off without damaging the electronic components after the processing is completed (hereinafter, also referred to as "high adhesion and easy peeling"). As a means for realizing high adhesion and easy peeling, for example, Patent Document 4 discloses an adhesive sheet using an adhesive in which a polyfunctional monomer or oligomer having a radiation-polymerizable functional group is bonded to the side chain or main chain of the polymer. By utilizing the fact that the polymer has a radiation-polymerizable functional group and is cured by exposure to ultraviolet light, the adhesive strength is reduced by exposure to ultraviolet light during peeling, allowing peeling without leaving any adhesive residue. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-052050 A [Patent Document 2] JP 2015-021067 A [Patent Document 3] JP 2015-120876 A [Patent Document 4] Japanese Patent Application Publication No. 5-32946 Summary of the Invention [Problem to be solved by the invention]
[0006] As electronic components become more powerful, the power applied to them tends to increase, and the time that the electronic components are used in high-temperature environments may increase. Therefore, adhesive films used to fix electronic components are required to have heat resistance in high-temperature environments. In addition, in order to impart high performance to electronic components, various processes have been carried out on electronic components. For example, in a process of forming a metal thin film on the surface of an electronic component by sputtering, a metal thin film with better conductivity can be formed by heating to a high temperature and performing high-temperature processing. In particular, in recent years, high-temperature processing steps have become hotter and longer, and adhesive films with high heat resistance (thermal decomposition resistance) are required. Generally, in order to provide adhesive films with high heat resistance, adhesives with high elasticity and hardness are sometimes used.
[0007] On the other hand, from the viewpoint of improving the handling property, an adhesive film having a substrate may be used. In an adhesive film having a substrate, if a hard adhesive is used to form an adhesive layer, the adhesive layer may peel off at the interface with the substrate when peeling off the separator protecting the adhesive layer because the adhesive layer has a low anchoring force to the substrate, which may make the film difficult to handle.
[0008] The present invention aims to provide an adhesive film that can achieve both high heat resistance and excellent handleability. Another aim of the present invention is to provide a method for producing an adhesive film that can achieve both high heat resistance and excellent handleability. [Means for solving the problem]
[0009] Disclosure 1 provides an adhesive film having an adhesive layer and a substrate, the adhesive layer containing a photocurable adhesive, and the adhesive layer is irradiated with a 405 nm wavelength, 80 mW / cm illuminance by an ultra-high pressure mercury lamp. 2 After 300 seconds of irradiation with light of 405 nm wavelength and 80 mW / cm irradiance, the adhesive layer has an anchor strength of 0.10 N / 25 mm or more at 23°C. 2 The tensile storage modulus at 23°C after 300 seconds of irradiation with light was 1.0×10 8 It is an adhesive film having a viscosity of 10 Pa or more. Disclosure 2 relates to an adhesive film having an adhesive layer and a substrate, the adhesive layer containing a photocurable adhesive, the adhesive film being attached to glass, and the adhesive layer in contact with the glass after irradiating light from the adhesive film side has an anchor strength of 0.10 N / 25 mm or more at 23° C. to the substrate, and the adhesive layer being attached to glass, and the adhesive layer in contact with the glass after irradiating light from the adhesive layer side has a tensile storage modulus of 1.0×10 at 23° C. 8 It is an adhesive film having a viscosity of 10 Pa or more. The present disclosure 3 is the adhesive film according to the present disclosure 1 or 2, in which at least one surface of the substrate has an easy-adhesion layer. The present disclosure 4 is an adhesive film according to the present disclosure 3, wherein the easy-adhesion layer includes at least one layer selected from a corona-treated layer, a plasma-treated layer, a sandblasted layer, a chemically etched layer, and a treatment-coated layer. The present disclosure 5 is the adhesive film according to the present disclosure 1, 2, 3 or 4, wherein the substrate has a glass transition temperature (Tg) of 100° C. or higher. Disclosure 6 is the adhesive film according to Disclosure 1, 2, 3, 4, or 5, wherein the substrate has a melting point of 150° C. or higher. The present disclosure 7 is the adhesive film according to the present disclosure 1, 2, 3, 4, 5 or 6, wherein the photocurable adhesive contains a curable resin, and the curable resin contains a compound having an imide bond. The present disclosure 8 is the adhesive film of the present disclosure 1, 2, 3, 4, 5, 6, or 7, wherein the adhesive layer has a glass transition temperature (Tg) of more than 0°C and less than 100°C in an uncured state. In the present disclosure 9, the adhesive layer is formed by irradiating the adhesive film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 After irradiating for 200 seconds, the peak probe tack value of the adhesive layer at 60° C. was 0.30 N / cm 2 The adhesive film of Disclosure 1, 2, 3, 4, 5, 6, 7 or 8 is as described above. Disclosure 10 is the adhesive film of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, or 9, having the adhesive layer on both sides of the substrate. The present disclosure 11 is the adhesive film of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, wherein the adhesive film has a water absorption rate of 0.60% or less when left standing for 1 day under conditions of 23°C and 50% RH. The adhesive film of the present disclosure 12 is the adhesive film of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11, which has a 10% weight loss temperature of 425° C. or higher. Disclosure 13 is an adhesive film according to Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 used for temporarily fixing electronic components. Disclosure 14 is a method for producing an adhesive film having an adhesive layer and a substrate, the adhesive layer containing a photocurable adhesive, the adhesive film being laminated to glass, and the adhesive layer in contact with the glass after irradiating the adhesive film with light has an anchor strength of 0.10 N / 25 mm or more at 23°C to the substrate, the method including a step of directly applying an adhesive to the substrate. The present disclosure 15 is a method for producing an adhesive film according to the present disclosure 14, comprising a step of performing at least one surface treatment selected from corona treatment, plasma treatment, sandblasting, chemical etching, and application of a treatment agent on at least one surface of the substrate. The present invention will be described in detail below. The adhesive film of the present disclosure 1 is also called the "adhesive film of the present invention 1," and the adhesive film of the present disclosure 2 is also called the "adhesive film of the present invention 2." Furthermore, matters common to the adhesive film of the present invention 1 and the adhesive film of the present invention 2 are not particularly specified or are described as the "adhesive film of the present invention."
[0010] The present inventors have investigated the use of a specific adhesive layer for an adhesive film having a substrate and an adhesive layer, and have adjusted the anchoring force of the cured adhesive layer to the substrate and the tensile storage modulus of the cured adhesive layer to specific values. As a result, they have found that an adhesive film that can achieve both high heat resistance and excellent handling properties can be obtained, and have completed the present invention.
[0011] The adhesive film of the present invention has a substrate. The substrate preferably contains a resin material having excellent heat resistance. Examples of the resin material include a resin (A1) having a repeating unit containing at least one selected from the group consisting of an ether bond, a ketone group, and an ester bond in the main chain skeleton, polyimide, polyamide, etc. Among them, the substrate preferably contains the resin (A1). By containing the resin (A1) in the substrate, the water absorption rate of the substrate is reduced, so that the generation of foaming during high-temperature processing can be more effectively suppressed, and peeling during high-temperature processing can be more effectively prevented. Such resin materials may be used alone or in combination of two or more kinds.
[0012] Examples of the resin (A1) include polyether ether ketone (PEEK), polyethylene naphthalate (PEN), polyamide resins, and the like.
[0013] At least one surface of the substrate preferably has an easy-adhesion layer. By having at least one surface of the substrate have an easy-adhesion layer, the adhesion between the adhesive layer and the substrate is improved, and the anchoring force of the adhesive layer to the substrate at 23°C is improved. As a result, the handleability of the obtained adhesive film is improved.
[0014] The easy-adhesion layer preferably includes at least one layer selected from a corona-treated layer, a plasma-treated layer, a sandblasted layer, a chemically etched layer, and a treatment-coated layer. The easy-adhesion layer includes at least one layer selected from a corona-treated layer, a plasma-treated layer, a sandblasted layer, a chemically etched layer, and a treatment-coated layer, which improves the adhesion between the adhesive layer and the substrate, thereby improving the anchoring force of the adhesive layer to the substrate at 23°C, and improving the handleability of the resulting adhesive film. In particular, it is more preferable that the easy-adhesion layer has a corona-treated layer. The method for forming the corona-treated layer may be, for example, to perform corona treatment on the substrate using a high-frequency power supply (such as "AGI-020" manufactured by Kasuga Electric Co., Ltd.) under conditions of output of 0.3 kW, electrode distance of 1 mm, and speed of 2 m / min to form a corona-treated layer. Alternatively, a commercially available product in which the substrate has been subjected to corona treatment may be used. Examples of the treating agent that forms the treating agent coating layer include polyethyleneimine graft polymers, acrylic polymers, polyimides, bismaleimide resins, silane coupling agents, titanium coupling agents, other known adhesion-imparting agents, and pressure-sensitive adhesives.
[0015] When the easy-adhesion layer is a treatment agent coating layer, the thickness of the treatment agent coating layer is preferably 0.1 μm in lower limit and 1000 μm in upper limit. By having the thickness of the treatment agent coating layer within the above range, the adhesion between the adhesive layer and the substrate is further improved, and the anchoring force of the adhesive layer to the substrate at 23° C. is further improved. As a result, the handleability of the obtained adhesive film is further improved. The more preferred lower limit of the thickness of the treatment agent coating layer is 1 μm, the more preferred upper limit is 200 μm, and the even more preferred upper limit is 100 μm. When the easy-adhesion layer is other than the treatment agent coating layer, the thickness of the easy-adhesion layer is not particularly limited, but is substantially 1 nm or more and 200 μm or less.
[0016] The lower limit of the glass transition temperature (Tg) of the substrate is preferably 100° C. When the substrate has a glass transition temperature of 100° C. or higher, the heat resistance of the resulting adhesive film is further improved. The lower limit of the glass transition temperature of the substrate is more preferably 120° C. When the substrate has a glass transition temperature, the upper limit of the glass transition temperature of the substrate is not particularly limited, but is substantially about 300°C. The glass transition temperature of the substrate can be measured, for example, by dynamic viscoelasticity measurement, etc. Specifically, for example, the glass transition temperature can be measured as the temperature at which the loss tangent has a maximum value by performing dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200" or the like) under measurement conditions of a tensile mode, a heating rate of 10°C / min, a measurement temperature of 0°C to 300°C, and a frequency of 10 Hz.
[0017] The lower limit of the melting point of the substrate is preferably 150° C. When the melting point of the substrate is 150° C. or higher, the heat resistance of the obtained adhesive film is further improved. When the base material has a melting point, the upper limit of the melting point of the base material is not particularly limited, but is substantially about 400°C. The melting point of the base material can be measured, for example, by the following method. That is, the substrate is subjected to differential scanning calorimetry (DSC) using a differential scanning calorimeter (e.g., "DSC-7020" manufactured by Hitachi High-Tech Science Corporation) under the measurement conditions of a nitrogen atmosphere, a heating rate of 10°C / min, and a measurement temperature of 30°C to 500°C, and the melting point of the substrate can be measured by reading the temperature showing the endothermic peak from the obtained differential scanning calorimetry curve.
[0018] The substrate preferably has a lower limit of 2% for the light transmittance at a wavelength of 405 nm (hereinafter, sometimes simply referred to as "light transmittance"). When the substrate has a light transmittance of 2% or more, a sufficient amount of light can be irradiated onto the adhesive layer, so that the adhesive layer of the adhesive film can be easily cured. The more preferable lower limit of the light transmittance of the substrate is 3%, and the even more preferable lower limit is 5%. The upper limit of the light transmittance of the substrate is preferably 98%. When the light transmittance of the substrate is 98% or less, irradiation of the adherend with light can be suppressed when the adhesive film is irradiated with light, so that the adhesive film can be cured while suppressing deterioration of the quality of the adherend. In this specification, the light transmittance at a wavelength of 405 nm can be measured by using a spectrophotometer (such as "V-670" manufactured by JASCO Corporation).
[0019] The upper limit of the thickness of the substrate is preferably 200 μm. By making the thickness of the substrate 200 μm or less, the adhesive layer of the adhesive film can be easily cured. The upper limit of the thickness of the substrate is more preferably 180 μm, and even more preferably 150 μm. The preferred lower limit of the thickness of the substrate is 5 μm. When the thickness of the substrate is 5 μm or more, the adhesive film obtained has a firmness and is more excellent in handleability. The more preferred lower limit of the substrate is 8 μm, and the even more preferred lower limit is 10 μm.
[0020] The thickness ratio of the substrate is preferably 5% at the lower limit with respect to the total thickness of the adhesive film of the present invention. When the thickness ratio of the substrate is 5% or more, the water absorption rate of the adhesive film described below can be easily adjusted to an appropriate range. The thickness ratio of the substrate is more preferably 10% at the lower limit, and even more preferably 15% at the lower limit. The upper limit of the thickness ratio of the substrate is preferably 70%. By making the thickness ratio of the substrate 70% or less, the manufacturing cost of the adhesive film of the present invention can be kept low. The upper limit of the thickness ratio of the substrate is more preferably 50%, and even more preferably 40%.
[0021] The adhesive film of the present invention has an adhesive layer. The adhesive layer contains a photocurable adhesive. The adhesive layer contains a photocurable adhesive, so that the adhesive layer has photocurability. Therefore, the adhesive layer can be cured by irradiation with light, so that the adhesion of the adhesive film during high-temperature processing can be suppressed, and the adhesive film can be easily peeled off at the time of peeling.
[0022] The photocurable adhesive preferably contains a curable resin. The curable resin preferably contains a compound having an imide bond. When the curable resin contains a compound having an imide bond, the adhesive layer has better heat resistance. In addition, since the compound having an imide bond has excellent light absorption properties, when the curable resin contains a compound having an imide bond, the adhesive layer can be cured more easily by irradiation with light.
[0023] The compound having the imide bond preferably contains a resin having an imide skeleton in the repeating unit of the main chain. The resin having the imide skeleton in the repeating unit of the main chain has excellent heat resistance due to the imide skeleton, and the main chain is unlikely to decompose even when subjected to high-temperature processing at 300°C or higher. Therefore, by containing a curable resin containing a resin having the imide skeleton in the repeating unit of the main chain, the adhesive film obtained has excellent heat resistance, and can further suppress outgassing during high-temperature processing, voids between the adherend, and lifting. In addition, when the adhesive film is used as a temporary fixing material, it can prevent adhesion enhancement to the adherend in a high-temperature environment and the occurrence of adhesive residue when peeled off from the adherend.
[0024] The resin having an imide skeleton in the repeating unit of the main chain preferably has a constitutional unit represented by the following formula (1).
[0025] [ka]
[0026] In the above formula (1), P 1 is preferably an aromatic group having 5 to 50 carbon atoms. 1is an aromatic group having 5 to 50 carbon atoms, the adhesive film obtained has better heat resistance. That is, outgassing during high-temperature processing, voids between the film and the adherend, and lifting can be more effectively prevented. In addition, when the adhesive film is used as a temporary fixing material, it is possible to more effectively prevent adhesion to the adherend in a high-temperature environment and to prevent adhesive residue from being left behind when peeled off from the adherend.
[0027] In the above formula (1), Q 1 is preferably a substituted or unsubstituted linear, branched or cyclic aliphatic group having 2 to 100 carbon atoms. 1 is a substituted or unsubstituted linear, branched or cyclic aliphatic group having from 2 to 100 carbon atoms, the adhesive film obtained has better light transmittance. In addition, the adhesive film obtained has better flexibility and can exhibit high conformability to an adherend having irregularities, and when the adhesive film is used as a temporary fixing material, it can be more easily peeled off. Also, the above Q 1 is preferably an aliphatic group derived from a diamine compound. In particular, from the viewpoints of light transparency, flexibility, and compatibility with solvents and other components of the resin having the imide skeleton in the main chain repeating unit, Q is preferably an aliphatic group derived from a diamine compound. 1 is preferably an aliphatic group derived from dimer diamine. The dimer diamine is a diamine compound obtained by reducing and amminating cyclic and acyclic dimer acids obtained as dimers of unsaturated fatty acids, and examples of the dimer diamine include linear, monocyclic, and polycyclic dimer diamines. The dimer diamine may contain a carbon-carbon double bond, or may be a hydrogenated product to which hydrogen has been added.
[0028] The aliphatic group derived from the dimer diamine is preferably at least one group selected from the group consisting of a group represented by the following formula (2-1), a group represented by the following formula (2-2), a group represented by the following formula (2-3), and a group represented by the following formula (2-4). Among these, the group represented by the following formula (2-2) is more preferred.
[0029] [ka]
[0030] In formulas (2-1) to (2-4), R 1 ~R 16 each independently represents a linear or branched hydrocarbon group, and * represents a bond. The bond * is bonded to N in the above formula (1).
[0031] In the above formulas (2-1) to (2-4), R 1 ~R 16 The hydrocarbon group represented by may be a saturated hydrocarbon group or an unsaturated hydrocarbon group. 1 and R 2 , R 3 and R 4 , R 5 and R 6 , R 7 and R 8 , R 9 and R 10 , R 11 and R 12 , R 13 and R 14 , and R 15 and R 16 The total number of carbon atoms is preferably 7 or more and 50 or less. When the total number of carbon atoms is within the above range, the obtained adhesive film has better light transmission and flexibility, and also has better compatibility with the solvent and other components of the resin having the imide skeleton in the main chain repeating unit. The total number of carbon atoms is more preferably 9 or more, even more preferably 12 or more, and even more preferably 14 or more. The total number of carbon atoms is more preferably 35 or less, even more preferably 25 or less, and even more preferably 18 or less.
[0032] In the group represented by the above formula (2-1), the group represented by the above formula (2-2), the group represented by the above formula (2-3), and the group represented by the above formula (2-4), the optical isomerism is not particularly limited and includes any optical isomerism.
[0033] The resin having an imide skeleton in a repeating unit of its main chain preferably includes a resin having no maleimide group and having an imide skeleton in a repeating unit of its main chain, and more preferably includes a resin having no polymerizable functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of its main chain.
[0034] The resin having no maleimide group and an imide skeleton in the repeating unit of the main chain preferably has a weight average molecular weight of 20,000 or more and 2,000,000 or less. When the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 20,000 or more, the obtained adhesive film has better heat resistance. That is, the occurrence of outgassing and voids between the adherend and the adhesive during high-temperature processing and lifting can be further suppressed. In addition, when the adhesive film is used as a temporary fixing material, it is possible to further prevent adhesion to the adherend in a high-temperature environment and the occurrence of adhesive residue when peeled off from the adherend. When the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 2,000,000 or less, the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain has better compatibility with solvents and other components. The weight average molecular weight of the resin that does not have a maleimide group and has an imide skeleton in the repeating unit of the main chain is more preferably 40,000 in lower limit and 600,000 in upper limit, still more preferably 50,000 in lower limit and still more preferably 300,000 in upper limit. In this specification, the weight average molecular weight is measured as a polystyrene equivalent molecular weight by gel permeation chromatography (GPC). Specifically, for example, the measurement can be performed using an APC system (manufactured by Waters) under the conditions of a mobile phase of THF, a flow rate of 1.0 mL / min, a column temperature of 40°C, a sample concentration of 0.2 mass%, and an RI-PDA detector. As the column, HR-MB-M 6.0 x 150 mm (manufactured by Waters) or the like can be used.
[0035] Specific examples of the resin that does not have a maleimide group and has an imide skeleton in the repeating unit of the main chain include resins that have a constitutional unit represented by the above formula (1) and have functional groups at both ends that do not have maleimide groups.
[0036] The resin having a constituent unit represented by the above formula (1) and a functional group not having a maleimide group at both ends may have a constituent unit represented by the following formula (3).
[0037] [ka]
[0038] In formula (3), P 2 represents an aromatic group, Q 2 represents a group having a substituted or unsubstituted aromatic structure.
[0039] In the above formula (3), P 2 is preferably an aromatic group having 5 to 50 carbon atoms. 2 is an aromatic group having 5 to 50 carbon atoms, the adhesive film obtained has better heat resistance. That is, the occurrence of outgassing, voids, and lifting between the support and the film during high-temperature processing can be further suppressed, and the occurrence of increased adhesion to the adherend and the occurrence of adhesive residue when peeled off from the adherend can be further prevented.
[0040] In the above formula (3), Q 2is preferably a substituted or unsubstituted group having an aromatic structure having 5 to 50 carbon atoms. 2 is a substituted or unsubstituted group having an aromatic structure with 5 to 50 carbon atoms, the adhesive film obtained has better heat resistance. That is, outgassing during high-temperature processing, voids between the film and the adherend, and lifting can be further suppressed. In addition, when the adhesive film is used as a temporary fixing material, it is possible to further prevent adhesion to the adherend from increasing in a high-temperature environment and to prevent adhesive residue from being left behind when peeled off from the adherend.
[0041] Examples of the functional group not having a maleimide group include an aliphatic group, an alicyclic group, an aromatic group, an acid anhydride group, an amino group, etc. Specific examples include an unreacted one-terminal constituent group of an acid anhydride or diamine compound that is a raw material for a resin not having a maleimide group and having an imide skeleton in a repeating unit of the main chain. In a resin having a structural unit represented by the above formula (1) and having functional groups at both ends that do not have maleimide groups, the functional groups at both ends that do not have maleimide groups may be the same or different.
[0042] The content of the structural unit represented by the above formula (1) in the resin having a functional group not having a maleimide group at both ends is preferably 30 mol % or more, more preferably 50 mol % or more, and is preferably 90 mol % or less, more preferably 80 mol % or less. When a resin having a structural unit represented by the above formula (1) and having a functional group not having a maleimide group at both ends has a structural unit represented by the above formula (3), the content of the structural unit represented by the above formula (3) is preferably 5 mol % or more, more preferably 10 mol % or more, even more preferably 20 mol % or more, and is preferably 50 mol % or less, more preferably 30 mol % or less. In the constitutional unit represented by the above formula (1) and the constitutional unit represented by the above formula (3), the content of each constitutional unit is within the above range, so that the adhesive film obtained can suppress outgassing during high-temperature processing, voids between the film and the adherend, and lifting. In addition, when the adhesive film is used as a temporary fixing material, it can be more easily peeled off from the adherend. The structural unit represented by the above formula (1) and the structural unit represented by the above formula (3) may have a block structure consisting of block components in which the respective structural units are arranged consecutively, or may have a random structure in which the respective structural units are arranged randomly.
[0043] Examples of a method for producing the resin having no maleimide group and an imide skeleton in the repeating unit of the main chain include a method of reacting a diamine compound with an aromatic acid anhydride.
[0044] As the diamine compound, either an aliphatic diamine compound or an aromatic diamine compound can be used. By using an aliphatic diamine compound as the diamine compound, the adhesive film obtained has better light transmittance, and has better flexibility, and can exhibit high conformability to an adherend having irregularities, and when the adhesive film is used as a temporary fixing material, it can be more easily peeled off. Furthermore, by using an aromatic diamine compound as the diamine compound, the adhesive film obtained has superior heat resistance. The diamine compounds may be used alone or in combination of two or more kinds.
[0045] Examples of the aliphatic diamine compound include 1,10-diaminodecane, 1,12-diaminododecane, dimer diamine, 1,2-diamino-2-methylpropane, 1,2-diaminocyclohexane, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,7-diaminoheptane, 1,8-diaminomenthane, 1,8-diaminooctane, 1,9-diaminononane, 3,3'-diamino-N-methyldipropylamine, diaminomaleonitrile, 1,3-diaminopentane, bis(4-amino-3-methylcyclohexyl)methane, 1,2-bis(2-aminoethoxy)ethane, and 3(4),8(9)-bis(aminomethyl)tricyclo(5.2.1.02,6)decane.
[0046] Among the above aliphatic diamine compounds, dimer diamine is preferred from the viewpoints of light transmittance, flexibility, and compatibility with solvents and other components of the resin that does not have the maleimide group and has an imide skeleton in the repeating unit of the main chain.Specific examples of the above dimer diamine include dimer diamines that can constitute at least one group selected from the group consisting of the group represented by the above formula (2-1), the group represented by the formula (2-2), the group represented by the formula (2-3), and the group represented by the formula (2-4).
[0047] Examples of the aromatic diamine compound include 9,10-diaminophenanthrene, 4,4'-diaminooctafluorobiphenyl, 3,7-diamino-2-methoxyfluorene, 4,4'-diaminobenzophenone, 3,4-diaminobenzophenone, 3,4-diaminotoluene, 2,6-diaminoanthraquinone, 2,6-diaminotoluene, 2,3-diaminotoluene, 1,8-diaminonaphthalene, 2,4-diaminotoluene, 2,5-diaminotoluene, 1,4-diaminoanthraquinone, 1,5-diaminotoluene, 1,6-diaminotoluene, 1,8 ... Aminoanthraquinone, 1,5-diaminonaphthalene, 1,2-diaminoanthraquinone, 2,4-cumenediamine, 1,3-bisaminomethylbenzene, 1,3-bisaminomethylcyclohexane, 2-chloro-1,4-diaminobenzene, 1,4-diamino-2,5-dichlorobenzene, 1,4-diamino-2,5-dimethylbenzene, 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, bis(amino-3-chlorophenyl)ethane, bis(4-amino-3,5-dimethylphenyl)methan , bis(4-amino-3,5-diethylphenyl)methane, 9,9'-bis(4-amino-3-ethylphenyl)fluorene, 2,3-diaminonaphthalene, 2,3-diaminophenol, bis(4-amino-5-methylphenyl)methane, bis(4-amino-3-methylphenyl)methane, bis(4-amino-3-ethylphenyl)methane, 4,4'-diaminophenylsulfone, 3,3'-diaminophenylsulfone, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenyl)phenyl)sulfone, 4,4'-Oxydianiline, 4,4'-Diaminodiphenyl Sulfide, 3,4'-Oxydianiline, 2,2-Bis(4-(4-aminophenoxy)phenyl)propane, 1,3-Bis(4-aminophenoxy)benzene, 4,4'-Bis(4-aminophenoxy)biphenyl, 4,4'-Diamino-3,3'-dihydroxybiphenyl, 4,4'-Diamino-3,3'-dimethylbiphenyl, 4,4'-Diamino-3,3'-dimethoxybiphenyl, Bisaniline M, Bisaniline P, 9,9-Bis(4-aminophenyl)fluorene, o-Tolidine Sulfone, 5,5'-Methylenebis(anthranilic acid), 1,Examples of the amines include 3-bis(4-aminophenoxy)-2,2-dimethylpropane, 1,3-bis(4-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)butane, 2,3,5,6-tetramethyl-1,4-phenylenediamine, 3,3',5,5'-tetramethylbenzidine, 4,4'-diaminobenzanilide, 2,2-bis(4-aminophenyl)hexafluoropropane, polyoxyalkylenediamines (e.g., Jeffamine D-230, D400, D-2000, and D-4000 manufactured by Huntsman), 1,3-cyclohexanebis(methylamine), m-xylylenediamine, and p-xylylenediamine.
[0048] Examples of the aromatic acid anhydride include pyromellitic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 1,2,4,5-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-biphenylethertetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, 3,4,9,10-perylenetetracarboxylic acid, 4,4'-sulfonyldiphthalic acid, 1-trifluoromethyl-2,3,5,6-benzenetetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)propane, 2,2-bis(2,3-dicarboxyphenyl)propane, 1,1 ... bis(3,4-dicarboxyphenyl)ethane, 1,1-bis(3,4-dicarboxyphenyl)ethane, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)sulfone, bis(3,4-dicarboxyphenyl)ether, benzene-1,2,3,4-tetracarboxylic acid, 2,3,2',3'-benzophenonetetracarboxylic acid, 2,3,3',4'-benzophenonetetracarboxylic acid, phenanthrene-1,8,9,10-tetracarboxylic acid, pyrazine-2,3,5,6-tetracarboxylic acid, thiophene-2,3,4,5-tetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide, 4,4'-(4,4'-isopropylidenediphenoxy)-bis(phthalic acid) and other carboxylic acid anhydrides.
[0049] The content of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is preferably 10 parts by mass at the lower limit and 90 parts by mass at the upper limit. When the content of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain is within this range, the adhesive film obtained can be more easily peeled off from the adherend when used as a temporary fixing material. From the viewpoint of further improving the peelability, the content of the resin having no maleimide group and having an imide skeleton in the repeating unit of the main chain is more preferably 20 parts by mass at the lower limit and 80 parts by mass at the upper limit.
[0050] The resin having the imide skeleton in the repeating unit of the main chain preferably contains a resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain. By containing a resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain, the adhesive film obtained is uniformly and quickly polymerized and crosslinked as a whole by irradiation with light, etc., and the elastic modulus increases, so that the adhesive force is greatly reduced. Therefore, when the adhesive film is used as a temporary fixing material, it is possible to more effectively prevent adhesion from being increased in a high-temperature environment or adhesive residue from being generated when peeled off. When the resin having an imide skeleton in a repeating unit of its main chain includes a resin which does not have the maleimide group and has an imide skeleton in a repeating unit of its main chain, it is preferable that the resin further includes a resin which has a functional group having a carbon-carbon double bond and has an imide skeleton in a repeating unit of its main chain, in addition to the resin which does not have a maleimide group and has an imide skeleton in a repeating unit of its main chain.
[0051] Examples of the functional group having a carbon-carbon double bond include an optionally substituted maleimide group, a citraconimide group, a vinyl ether group, an allyl group, and a (meth)acryloyl group. Among them, an optionally substituted maleimide group is preferred because it provides higher heat resistance. Note that the carbon-carbon double bond contained in an aromatic ring is not considered as the carbon-carbon double bond of the functional group having a carbon-carbon double bond. In this specification, "(meth)acryloyl" means acryloyl or methacryloyl.
[0052] The resin having the functional group having a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain preferably has a functional group equivalent (weight average molecular weight / number of functional groups having a carbon-carbon double bond) of 4000 or less. When the functional group equivalent of the functional group having a carbon-carbon double bond is 4000 or less, the obtained adhesive film has better heat resistance. This is considered to be because the resin molecule has a functional group having a carbon-carbon double bond at a density of at least a certain level, thereby shortening the distance between crosslinks and thereby suppressing adhesion enhancement. The functional group equivalent of the functional group having a carbon-carbon double bond is more preferably 3000 or less, and even more preferably 2000 or less. Further, there is no particular preferred lower limit for the functional group equivalent weight of the functional group having a carbon-carbon double bond, but the substantial lower limit is about 600.
[0053] The resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain preferably has a weight average molecular weight of 1000 or more and 100,000 or less. The resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 1000 or more, which makes it easy to form the adhesive film obtained, and the adhesive film obtained exhibits a certain degree of flexibility, so that it can exhibit high conformability to an adherend having unevenness, and when the adhesive film is used as a temporary fixing material, it can be peeled off more easily. The resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain has a weight average molecular weight of 100,000 or less, which prevents the solubility of the resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain in a solvent from becoming too low. The weight average molecular weight of the resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain is more preferably 1,500 or more and 50,000 or less, and further preferably 2,000 or more and less than 20,000.
[0054] In the resin having a functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of the main chain, the functional group having a carbon-carbon double bond may be present either at a side chain or at a terminal, but is preferably present at both terminals, and more preferably present at the side chain in addition to both terminals. The functional groups having a carbon-carbon double bond at both ends of the resin having the above-mentioned functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain are highly reactive, and can more fully cure the above-mentioned adhesive film by irradiation with light, etc. Therefore, when the adhesive film is used as a temporary fixing material, it is possible to more effectively prevent adhesion from increasing in a high-temperature environment and the occurrence of adhesive residue when peeled off. Furthermore, by having the functional group having the carbon-carbon double bond and the functional group having the carbon-carbon double bond in the side chain of the resin having the imide skeleton in the repeating unit of the main chain, the obtained adhesive film has better heat resistance. This is thought to be because the crosslinking distance is shortened, which further suppresses adhesion enhancement. In addition, by having the functional group having the carbon-carbon double bond and the functional group having the carbon-carbon double bond in the side chain of the resin having the imide skeleton in the repeating unit of the main chain, it becomes easy to adjust the functional group equivalent to 4000 or less while making the weight average molecular weight 1000 or more. This allows the adhesive film to have sufficient initial adhesive strength, and at the same time, it is possible to more effectively prevent adhesion enhancement and the occurrence of adhesive residue when peeled off.
[0055] As described above, in the resin having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, the functional group having the carbon-carbon double bond may be in either the side chain or the terminal. When either the side chain or the terminal is a functional group other than the functional group having a carbon-carbon double bond (functional group having no carbon-carbon double bond), the functional group having no carbon-carbon double bond may be, for example, an aliphatic group, an alicyclic group, an aromatic group, an acid anhydride group, an amino group, etc. Specifically, the functional group having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain may be an acid anhydride, an unreacted one-end constituent group of a diamine compound, etc., which is a raw material for the resin having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain. When the resin having the functional group having the carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain has two or more functional groups having no carbon-carbon double bond in the side chain or the terminal, the functional groups having no carbon-carbon double bond may be the same or different.
[0056] Specific examples of the resin having a functional group having a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain include resins having a constitutional unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of the terminal and the side chain.
[0057] The resin having a structural unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of an end and a side chain may have at least one structural unit selected from the group consisting of a structural unit represented by the following formula (4-1) and a structural unit represented by the following formula (4-2).
[0058] [ka]
[0059] In formula (4-1), P 3 represents an aromatic group, Q 3 represents a group having a substituted or unsubstituted aromatic structure, and in formula (4-2), P 4 represents an aromatic group, R represents a substituted or unsubstituted branched aliphatic group or aromatic group, and X represents a functional group having a carbon-carbon double bond.
[0060] P in the above formula (4-1) 3 and P in the above formula (4-2) 4 is preferably an aromatic group having 5 to 50 carbon atoms. 3 and P 4 By being an aromatic group having 5 to 50 carbon atoms, the adhesive film obtained has better heat resistance. That is, outgassing during high-temperature processing, voids between the film and the adherend, and lifting can be more effectively prevented. In addition, when the adhesive film is used as a temporary fixing material, it is possible to more effectively prevent adhesion to the adherend from increasing in a high-temperature environment and to prevent adhesive residue from being left behind when peeled off from the adherend.
[0061] In the above formula (4-1), Q 3 is preferably a substituted or unsubstituted group having an aromatic structure having 5 to 50 carbon atoms. 3is a substituted or unsubstituted group having an aromatic structure having 5 to 50 carbon atoms, the adhesive film obtained has better heat resistance. That is, outgassing during high-temperature processing, voids between the adhesive film and the adherend, and lifting can be further suppressed, and when the adhesive film is used as a temporary fixing material, adhesion to the adherend is enhanced in a high-temperature environment, and adhesive residue is further prevented from being left behind when the adhesive film is peeled off from the adherend.
[0062] In the above formula (4-2), R is preferably a substituted or unsubstituted branched aliphatic or aromatic group having 2 to 100 carbon atoms. When R is a substituted or unsubstituted branched aliphatic or aromatic group having 2 to 100 carbon atoms, the obtained adhesive film has excellent flexibility and can exhibit high conformability to an adherend having irregularities, and when the adhesive film is used as a temporary fixing material, it can be peeled off more easily.
[0063] In the above formula (4-2), R is an aromatic group having an aromatic ester group or an aromatic ether group, and the aromatic ester group or the aromatic ether group in R is preferably bonded to X. Here, the term "aromatic ester group" means a group in which an ester group is directly bonded to an aromatic ring, and the term "aromatic ether group" means a group in which an ether group is directly bonded to an aromatic ring. By making the moiety bonded to the ester group or ether group an aromatic group in this way, the obtained adhesive film has better heat resistance. That is, the occurrence of outgassing, voids, and lifting during high-temperature processing can be further suppressed. In addition, when the adhesive film is used as a temporary fixing material, it is possible to further prevent adhesion enhancement to the adherend in a high-temperature environment and the occurrence of adhesive residue when peeled from the adherend. On the other hand, by bonding X to R via an aromatic ester group or an aromatic ether group, the carbon-carbon double bond in X is not conjugated with R, and therefore does not hinder polymerization and crosslinking when heated or irradiated with light.
[0064] The content of the structural unit represented by the above formula (1) in the resin having a functional group having a carbon-carbon double bond at least in one of an end or a side chain is preferably 30 mol % or more, more preferably 50 mol % or more, and is preferably 90 mol % or less, more preferably 80 mol % or less. When a resin having a structural unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of an end and a side chain has a structural unit represented by the above formula (4-1), the content of the structural unit represented by the above formula (4-1) is preferably 5 mol % or more, more preferably 10 mol % or more, even more preferably 20 mol % or more, and is preferably 50 mol % or less, more preferably 30 mol % or less. When a resin having a structural unit represented by the above formula (1) and having a functional group having a carbon-carbon double bond at least in one of an end and a side chain has a structural unit represented by the above formula (4-2), the content of the structural unit represented by the above formula (4-2) is preferably 10 mol % or more, more preferably 20 mol % or more, and preferably 50 mol % or less, more preferably 30 mol % or less. In the constitutional unit represented by the above formula (1), the constitutional unit represented by the above formula (4-1), and the constitutional unit represented by the above formula (4-2), the content of each constitutional unit is within the above range, so that the adhesive film obtained can suppress outgassing during high-temperature processing, voids between the film and the adherend, and lifting. In addition, when the adhesive film is used as a temporary fixing material, it can be more easily peeled off from the adherend. The structural unit represented by the above formula (1), the structural unit represented by the above formula (4-1), and the structural unit represented by the above formula (4-2) may have a block structure consisting of block components in which the respective structural units are arranged consecutively, or may have a random structure in which the respective structural units are arranged randomly.
[0065] Examples of a method for producing a resin having a functional group with a carbon-carbon double bond and an imide skeleton in a repeating unit of the main chain include the following methods. That is, first, a diamine compound is reacted with an aromatic acid anhydride to prepare an imide compound. Then, a compound having a functional group reactive with the functional group and a functional group having a carbon-carbon double bond (hereinafter, also referred to as a "functional group-containing unsaturated compound") is reacted with the functional group of the imide compound to obtain a resin having the functional group having the carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain. Alternatively, a resin having a functional group having a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain can be obtained by reacting a diamine compound with an aromatic acid anhydride to prepare an imide compound and then reacting the terminal of the imide compound with, for example, maleic anhydride.
[0066] As the diamine compound and aromatic acid anhydride used in the method for producing a resin having a functional group with a carbon-carbon double bond and having an imide skeleton in a repeating unit of the main chain, the same compounds as those used in the method for producing a resin having no maleimide group and having an imide skeleton in a repeating unit of the main chain can be used.
[0067] The functional group-containing unsaturated compound is selected according to the functional group at the end or side chain of the imide compound. For example, when the functional group at the end or side chain of the imide compound is a hydroxyl group, examples of the functional group-containing unsaturated compound include a maleimide compound having a carboxy group, a vinyl compound having an ether group, an allyl compound having a glycidyl group, an allyl ether compound having a glycidyl group, a vinyl ether compound having a glycidyl group, an allyl compound having an isocyanate group, and a (meth)acryloyl compound having an isocyanate group. Furthermore, for example, when the functional group at the end or side chain of the imide compound is a carboxy group, examples of the functional group-containing unsaturated compound include an allyl compound having a hydroxyl group, an allyl compound having a glycidyl group, an allyl ether compound having a glycidyl group, and a vinyl ether compound having a glycidyl group. Examples of the maleimide compound having a carboxy group include maleimide acetate, maleimidopropionic acid, maleimidobutyric acid, maleimidohexanoic acid, trans-4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid, and 19-maleimido-17-oxo-4,7,10,13-tetraoxa-16-azanonadecanoic acid. An example of the vinyl compound having an ether group is butyl vinyl ether. An example of the allyl compound having a glycidyl group is diallyl monoglycidyl isocyanurate. Examples of the allyl ether compound having a glycidyl group include allyl glycidyl ether, glycerin diallyl monoglycidyl ether, and the like. Examples of the vinyl ether compound having a glycidyl group include glycidyloxyethyl vinyl ether, glycidyloxybutyl vinyl ether, glycidyloxyhexyl vinyl ether, glycidyl diethylene glycol vinyl ether, and glycidyl cyclohexane dimethanol monovinyl ether. The allyl compound having an isocyanate group includes, for example, allyl isocyanate. Examples of the (meth)acryloyl compound having an isocyanate group include 2-(meth)acryloyloxyethyl isocyanate. Examples of the allyl compound having a hydroxyl group include trimethylolpropane diallyl ether and pentaerythritol triallyl ether.
[0068] The content of the resin having the functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is preferably 10 parts by mass, and preferably 100 parts by mass. When the content of the resin having the functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is within this range, the adhesive film can be more easily peeled off at the time of peeling. From the viewpoint of further improving the peelability, the content of the resin having the functional group having a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain in 100 parts by mass of the curable resin is more preferably 20 parts by mass, even more preferably 30 parts by mass, and more preferably 90 parts by mass, even more preferably 80 parts by mass, and even more preferably 70 parts by mass.
[0069] When the compound having an imide bond does not have the maleimide group and contains a resin having an imide skeleton in a repeating unit of the main chain, it is preferable that the compound having an imide bond further contains a polyfunctional monomer or polyfunctional oligomer (hereinafter simply referred to as "polyfunctional monomer or polyfunctional oligomer") having two or more functional groups having a carbon-carbon double bond in the molecule and having a molecular weight of 5,000 or less. In addition, when the compound having an imide bond has the functional group having a carbon-carbon double bond and contains a resin having an imide skeleton in a repeating unit of the main chain, the compound having an imide bond may further contain the polyfunctional monomer or polyfunctional oligomer. By containing the above-mentioned multifunctional monomer or multifunctional oligomer, the adhesive film can be more efficiently three-dimensionally reticulated by irradiation with light, etc., and in particular, when the adhesive film is used as a temporary fixing material, it is possible to more effectively prevent increased adhesion in high temperature environments and the occurrence of adhesive residue when peeled off.
[0070] In addition, when the resin having the imide skeleton in the repeating unit of the main chain is not reactive, the curable resin needs to have reactivity as a whole by further containing another component having a reactive functional group. As such another component having a reactive functional group, it is preferable to use the polyfunctional monomer or polyfunctional oligomer. As an example of a case where the resin having the imide skeleton in the repeating unit of the main chain is not reactive, for example, the resin having the imide skeleton in the repeating unit of the main chain does not have the maleimide group and only contains a resin having the imide skeleton in the repeating unit of the main chain.
[0071] Examples of the functional group having a carbon-carbon double bond in the polyfunctional monomer or oligomer include an optionally substituted maleimide group, a citraconimide group, a vinyl ether group, an allyl group, and a (meth)acryloyl group. Among them, an optionally substituted maleimide group is preferred because it provides higher heat resistance. In particular, the polyfunctional monomer or oligomer is preferably a bismaleimide compound.
[0072] The polyfunctional monomer or oligomer preferably has a group derived from a diamine compound. As the diamine compound, either an aliphatic diamine compound or an aromatic diamine compound can be used, but an aliphatic diamine compound is preferred. That is, the polyfunctional monomer or oligomer more preferably has an aliphatic group derived from a diamine compound. By using an aliphatic diamine compound as the diamine compound, the adhesive film obtained has better light transmittance. In addition, the adhesive film obtained has better flexibility, can exhibit high conformability to an adherend having unevenness, and can be more easily peeled off when used as a temporary fixing material.
[0073] Among the above aliphatic diamine compounds, the above dimer diamines are preferred from the viewpoints of light transmittance, flexibility, and compatibility with the solvent of the polyfunctional monomer or polyfunctional oligomer and other components.
[0074] The content of the polyfunctional monomer or polyfunctional oligomer in 100 parts by mass of the curable resin is preferably 5 parts by mass at the lower limit and 90 parts by mass at the upper limit. When the content of the polyfunctional monomer or polyfunctional oligomer is within this range, the adhesive film can be more easily peeled off. From the viewpoint of further improving the peelability, the content of the polyfunctional monomer or polyfunctional oligomer is more preferably 10 parts by mass at the lower limit and 50 parts by mass at the upper limit.
[0075] When the compound having an imide bond contains a resin having a functional group with a carbon-carbon double bond and an imide skeleton in the repeating unit of the main chain, and the polyfunctional monomer or oligomer, the preferred lower limit of the total content of the resin having a functional group with a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, and the polyfunctional monomer or oligomer in 100 parts by mass of the curable resin is 20 parts by mass, and the preferred upper limit is 80 parts by mass. When the total content of the resin having a functional group with a carbon-carbon double bond and having an imide skeleton in the repeating unit of the main chain, and the polyfunctional monomer or oligomer is within this range, the adhesive film can be more easily peeled off at the time of peeling. From the viewpoint of further improving the releasability, the lower limit of the total content of the resin having a functional group having a carbon-carbon double bond and having an imide skeleton in a repeating unit of its main chain, and the polyfunctional monomer or polyfunctional oligomer is more preferably 30 parts by mass, even more preferably 40 parts by mass, still more preferably 50 parts by mass, and more preferably 70 parts by mass.
[0076] The compound having an imide bond preferably includes a compound having a maleimide group. By including the compound having a maleimide group, the adhesive film obtained has better heat resistance. The compound having a maleimide group is preferably a bismaleimide compound, or a resin having a maleimide group and an imide skeleton in a repeating unit of the main chain. That is, the compound having an imide bond preferably includes the bismaleimide compound as the polyfunctional monomer or polyfunctional oligomer, or the compound having an imide bond preferably includes a functional group having a carbon-carbon double bond, and the resin having an imide skeleton in a repeating unit of the main chain preferably includes a resin having a maleimide group as the functional group having a carbon-carbon double bond.
[0077] The photocurable adhesive preferably contains a photopolymerization initiator. By including a photopolymerization initiator in the photocurable adhesive, the photocurable adhesive cures more easily and increased adhesion of the resulting adhesive film to the substrate during high-temperature processing can be more effectively suppressed, so that the resulting adhesive film has improved releasability from the substrate and can be more easily peeled off from the substrate.
[0078] The photopolymerization initiator may be, for example, one that is activated by irradiation with light having a wavelength of 250 to 800 nm. In particular, the photopolymerization initiator has a molar absorption coefficient at 405 nm of preferably 10 ml / (g cm) or more, more preferably 200 ml / (g cm), and even more preferably 405 ml / (g cm), since it is unlikely to overlap with the absorption wavelength of the curable resin and is sufficiently activated when the adhesive film is irradiated with light. The molar absorption coefficient at 405 nm has no particular upper limit, but is preferably 1.0×10 6 The practical upper limit is about ml / (g cm).
[0079] Examples of the photopolymerization initiator include acetophenone derivatives, benzoin ether compounds, ketal derivatives, and phosphine oxide derivatives. The acetophenone derivatives include, for example, methoxyacetophenone. Examples of the benzoin ether compounds include benzoin propyl ether and benzoin isobutyl ether. Examples of the ketal derivative include benzyl dimethyl ketal and acetophenone diethyl ketal. Further, examples of the photopolymerization initiator include bis(η5-cyclopentadienyl)titanocene derivative compounds, benzophenone, Michler's ketone, chlorothioxanthone, dodecylthioxanthone, dimethylthioxanthone, diethylthioxanthone, α-hydroxycyclohexylphenyl ketone, and 2-hydroxymethylphenylpropane. These photopolymerization initiators may be used alone or in combination of two or more kinds.
[0080] The content of the polymerization initiator is preferably 0.1 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the polymerization initiator being within this range, the adhesive film is uniformly and quickly polymerized and crosslinked as a whole by irradiation with light or the like, and the elastic modulus increases, so that the adhesive strength is greatly reduced. In particular, when the adhesive film is used as a temporary fixing material, it is possible to prevent adhesion from being increased in a high-temperature environment or the occurrence of adhesive residue when peeled off. The more preferable lower limit of the content of the polymerization initiator is 0.3 parts by mass, and the more preferable upper limit is 3 parts by mass.
[0081] The photocurable adhesive preferably further contains an inorganic filler. By containing the above-mentioned inorganic filler, the adhesive film obtained can suppress the decrease in elastic modulus at high temperatures, and peeling during high-temperature processing can be further suppressed even when high-temperature processing at 300°C or higher is performed.
[0082] Examples of the inorganic filler include at least one inorganic filler selected from the group consisting of oxides of silicon, titanium, aluminum, calcium, boron, magnesium, and zirconia, and composites thereof. Among these, silica and talc are preferred because they are commercially available at low cost and easily available.
[0083] The inorganic filler may be surface-modified. Examples of the functional group that may be used to modify the surface of the inorganic filler include an alkylsilane group, a methacryloyl group, and a dimethylsiloxane group. Among these, the dimethylsiloxane group is preferred because it has a suitable hydrophobicity.
[0084] The preferred lower limit of the average particle size of the inorganic filler is 5 nm, and the preferred upper limit is 30 μm. By the average particle size of the inorganic filler being within this range, the obtained adhesive film can be more suppressed from peeling off under high temperature conditions, and when the adhesive film is used as a temporary fixing material, it can be peeled off by peeling treatment. The more preferred lower limit of the average particle size of the inorganic filler is 10 nm, and the more preferred upper limit is 20 μm, and the even more preferred lower limit is 15 nm, and the even more preferred upper limit is 15 μm. The average particle size can be determined, for example, by observing 50 particles of any inorganic filler using an electron microscope or an optical microscope and calculating the average particle size of each inorganic filler, or by performing laser diffraction particle size distribution measurement.
[0085] The content of the inorganic filler is preferably 1 part by mass at the lower limit and 20 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the inorganic filler being within this range, the obtained adhesive film can be more suppressed from peeling off in a high temperature environment, and when the adhesive film is used as a temporary fixing material, it can be peeled off by peeling treatment at the time of peeling. The more preferred lower limit of the content of the inorganic filler is 3 parts by mass, the more preferred upper limit is 15 parts by mass, the even more preferred lower limit is 5 parts by mass, and the even more preferred upper limit is 10 parts by mass.
[0086] When the adhesive film of the present invention is used as a temporary fixing material, the photocurable adhesive preferably further contains a surface conditioner. By containing the surface conditioner in the photocurable adhesive, the surface conditioner bleeds out to the adherend interface, and the removability of the obtained adhesive film is further improved. Examples of the surface conditioner include silicone-based surface conditioners, fluorine-based surface conditioners, acrylic surface conditioners, etc. These surface conditioners have excellent heat resistance, and therefore, by including these surface conditioners in the photocurable adhesive, the photocurable adhesive can be prevented from burning even after high-temperature processing at 300° C. or higher, and further, when the adhesive film obtained is peeled off, the surface conditioners bleed out to the adherend interface, making the peeling easier. Among these, silicone-based surface conditioners are preferred from the viewpoint of environmental friendliness and ease of disposal, and acrylic-based surface conditioners are preferred from the viewpoint of preventing contamination of the adherend by silicone.
[0087] The surface conditioner may have a functional group capable of crosslinking with a resin having the imide skeleton in the repeating unit of the main chain. When the surface conditioner has a functional group capable of crosslinking with a resin having the imide skeleton in the repeating unit of the main chain, the surface conditioner is chemically reacted with the resin having the imide skeleton in the repeating unit of the main chain or the polyfunctional monomer or polyfunctional oligomer by irradiation with light or reaction with a crosslinking agent, etc., and is incorporated. This makes it possible to prevent the surface conditioner from adhering to the adherend and contaminating it. Examples of functional groups capable of crosslinking with the resin having the imide skeleton in the repeating unit of the main chain or the polyfunctional monomer or polyfunctional oligomer include, for example, a carboxy group, a functional group having a radically polymerizable unsaturated bond (for example, a vinyl group, a (meth)acryloyl group, or a maleimide group which may be substituted), a hydroxy group, an amide group, an isocyanate group, and an epoxy group.
[0088] Examples of the silicone surface conditioner include silicone oil, silicone diacrylate, silicone graft copolymer, etc. Specifically, a silicone compound having a siloxane skeleton in the main chain and a functional group having a carbon-carbon double bond in the side chain or at the end is preferred. The silicone compound having a siloxane skeleton in the main chain and a functional group having a carbon-carbon double bond in the side chain or at the end is preferably at least one selected from the group consisting of a silicone compound represented by the following formula (5-1), a silicone compound represented by the following formula (5-2), and a silicone compound represented by the following formula (5-3): These silicone compounds are particularly excellent in heat resistance and have high polarity, so that they easily bleed out from the photocurable adhesive.
[0089] [ka]
[0090] X in the above formulae (5-1) to (5-3) and Y in the above formulae (5-1) and (5-3) each independently represent an integer of 0 or more and 1200 or less, and R in the above formulae (5-1) to (5-3) represents a functional group having a carbon-carbon double bond.
[0091] In the above formulas (5-1) to (5-3), examples of the functional group having a carbon-carbon double bond represented by R include an optionally substituted maleimide group, a citraconimide group, a vinyl ether group, an allyl group, and a (meth)acryloyl group. Among them, an optionally substituted maleimide group is preferred because the resulting adhesiveness has better heat resistance. In addition, when there are multiple Rs in the above formulas (5-1) to (5-3), each R may be the same or different.
[0092] Among the silicone compounds represented by the above formulas (5-1) to (5-3), commercially available examples include EBECRYL350, EBECRYL1360 (both manufactured by Daicel-Allnex Corporation), etc. Other examples include BYK-UV3500 (manufactured by BYK-Chemie Corporation), TEGO RAD2250 (manufactured by Evonik Corporation) (in both cases, R is an acryloyl group), etc.
[0093] The fluorine-based surface conditioner may be any compound containing fluorine in its structure, and examples thereof include Megafac RS-75, Megafac RS-90, Megafac F-556 (all manufactured by DIC Corporation), Fclear UVH-2 (manufactured by Kanto Denka Kogyo Co., Ltd.), Ftergent 601ADH2 (manufactured by Neos Corporation), and Acriit 8FX-038EX (manufactured by Taisei Fine Chemical Co., Ltd.).
[0094] Examples of the acrylic surface conditioner include acrylic copolymers used to impart leveling properties, and specific examples thereof include BYK-394, BYK-350, BYK-381 (all manufactured by BYK-Chemie), Disparlon 1970 (manufactured by Kusumoto Chemical Industries, Ltd.), and the like.
[0095] The content of the surface conditioner is preferably 0.1 parts by mass at the lower limit and 20 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the surface conditioner being within this range, the obtained adhesion is excellent in peeling performance without contaminating the adherend. From the viewpoint of further improving peeling performance while suppressing contamination, the more preferable lower limit of the content of the surface conditioner is 0.3 parts by mass, and the more preferable upper limit is 10 parts by mass. In addition, since the adhesive film of the present invention has excellent heat resistance, it can exert a sufficient effect even if the content of the surface conditioner is relatively small, and therefore, the possibility of contamination by the silicone compound or fluorine compound can be further reduced.
[0096] When the adhesive film of the present invention is used as a temporary fixing material, the photocurable adhesive may further contain a gas generating agent. By containing the gas generating agent, even after high-temperature processing at 300°C or higher, the gas generated by irradiation with light or the like is released at the interface with the adherend, so that the adherend can be peeled off more easily and without leaving any adhesive residue. In addition, even when a thin adherend is peeled off after high-temperature processing at 300°C or higher, damage to the adherend can be prevented.
[0097] The gas generating agent preferably has a weight loss rate of 5% or less at 300°C when heated from 30°C to 300°C at a heating rate of 10°C / min in a nitrogen atmosphere in TG-DTA (thermogravimetry-differential thermal analysis) measurement. If the weight loss rate is 5% or less, the gas generating agent is less likely to decompose even when a high-temperature processing treatment is performed at 300°C or higher, and the adhesive film has better heat resistance. That is, peeling can be further suppressed during high-temperature processing. In addition, it is possible to further prevent adhesion from increasing in a high-temperature environment and the occurrence of adhesive residue when peeled off. The above TG-DTA (thermogravimetry-differential thermal analysis) measurement can be carried out using, for example, a TG-DTA device (manufactured by Hitachi High-Tech Science Corporation, "STA7200RV") or the like.
[0098] Examples of the gas generating agent include a gas generating agent that generates gas by heating, a gas generating agent that generates gas by irradiating light, etc. These gas generating agents may be used alone or in combination of two or more. Among them, a gas generating agent that generates gas by irradiating light is preferred, and a gas generating agent that generates gas by irradiating light is more preferred. Examples of the gas generating agent include tetrazole compounds or their salts, triazole compounds or their salts, azo compounds, azide compounds, xanthone acetate, carbonates, etc. These gas generating agents may be used alone or in combination of two or more. Among them, tetrazole compounds or their salts are preferred because of their excellent heat resistance.
[0099] The content of the gas generating agent is preferably 5 parts by mass at the lower limit and 50 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the gas generating agent being within this range, the adhesive film obtained has particularly excellent peelability. The more preferred lower limit of the content of the gas generating agent is 8 parts by mass, and the more preferred upper limit is 30 parts by mass.
[0100] The adhesive layer may contain known additives, such as a photosensitizer, a heat stabilizer, an antioxidant, an antistatic agent, a plasticizer, a surfactant, and a wax.
[0101] The adhesive layer has a preferable lower limit of anchor strength to the substrate at 23° C. in an uncured state of 0.03 N / 25 mm. When the adhesive layer has an anchor strength to the substrate at 23° C. of 0.03 N / 25 mm or more, peeling at the interface between the adhesive layer and the substrate can be suppressed, and the handleability of the resulting adhesive film can be improved. A more preferable lower limit of the anchor strength to the substrate at 23° C. of the adhesive layer is 0.05 N / 25 mm. Further, although there is no particular upper limit to the anchoring strength of the adhesive layer to the substrate at 23° C., a practical upper limit is about 20 N / 25 mm. The anchoring strength of the adhesive layer to the substrate at 23° C. is measured by the following method. That is, one side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") is attached to a SUS plate that has been washed with ethanol and then wiped dry, and the adhesive layer of the adhesive film of the present invention that is not to be measured is overlapped with the other side of the double-sided tape, with the adhesive layer of the adhesive film of the present invention to be measured facing up. Furthermore, a 25 mm wide silicone tape (manufactured by Sliontec Co., Ltd., "6260-01") is pressed onto the adhesive layer of the adhesive film of the present invention by moving a 2 kg hand roller back and forth once at a speed of 300 mm / min. A 25 mm wide cut is made along the silicone tape for the adhesive layer pressed onto the silicone tape, and the test sample is prepared by curing at 23°C and 50% RH for 1 hour. The obtained test sample is subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "AG-IS" or the like) in accordance with JIS Z0237, and the adhesive layer pressed onto the silicon tape is peeled off from the substrate to measure the 90° peel strength of the adhesive layer against the substrate. The obtained 90° peel strength is regarded as the anchor strength of the adhesive layer against the substrate at 23°C.
[0102] When the adhesive film of the present invention is a single-sided adhesive film, the anchoring strength of the adhesive layer to the substrate at 23° C. is measured by the following method. That is, one side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") is attached to a SUS plate that has been washed with ethanol and then wiped dry, and then the side of the adhesive film of the present invention on which no adhesive layer is provided is overlapped with the other side of the double-sided tape, with the side of the adhesive film of the present invention on which the adhesive layer to be measured is placed up. Furthermore, a 25 mm wide silicon tape (manufactured by Sliontec Co., Ltd., "6260-01") is pressed onto the adhesive layer of the adhesive film of the present invention by moving a 2 kg hand roller back and forth once at a speed of 300 mm / min. A 25 mm wide cut is made along the silicon tape for the adhesive layer pressed onto the silicon tape, and the test sample is prepared by curing at 23°C and 50% RH for 1 hour. The obtained test sample is subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "AG-IS" or the like) in accordance with JIS Z0237, and the adhesive layer pressed onto the silicon tape is peeled off from the substrate to measure the 90° peel strength of the adhesive layer against the substrate. The obtained 90° peel strength is regarded as the anchor strength of the adhesive layer against the substrate at 23°C.
[0103] In the adhesive film of the first aspect of the present invention, the adhesive layer is formed by irradiating the adhesive film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2The lower limit of the anchoring force to the substrate at 23°C after irradiation with light of wavelength 405 nm for 300 seconds (hereinafter, sometimes simply referred to as "anchoring force of the adhesive layer to the substrate at 23°C after irradiation with light of wavelength 405 nm") is 0.10 N / 25 mm. When the anchoring force of the adhesive layer to the substrate at 23°C after irradiation with light of wavelength 405 nm is 0.10 N / 25 mm or more, peeling at the interface between the adhesive layer and the substrate can be suppressed, and the handleability of the resulting adhesive film is improved. The preferred lower limit of the anchoring force of the adhesive layer to the substrate at 23°C after irradiation with light of wavelength 405 nm is 0.15 N / 25 mm. Further, there is no particular preferred upper limit to the anchoring force of the adhesive layer to the substrate at 23° C. after irradiation with light having a wavelength of 405 nm, but a practical upper limit is about 20 N / 25 mm. The anchor strength of the adhesive layer to the substrate at 23°C after irradiation with light of 405 nm wavelength was measured by the following method: the adhesive layer was attached to a SUS plate using commercially available double-sided tape, and then irradiated with light of 405 nm wavelength and 80 mW / cm illuminance using an ultra-high pressure mercury lamp. 2 The measurement can be performed by using the above adhesive film irradiated with light of 405 nm for 300 seconds. When the adhesive film is a one-sided adhesive film, the direction of irradiating the adhesive film with light of 405 nm wavelength from an ultra-high pressure mercury lamp may be from the substrate side or from the adhesive layer side. When irradiating light from the adhesive layer side, irradiation is performed without removing the separator protecting the adhesive layer.
[0104] In the adhesive film of the present invention 2, the adhesive film is laminated to glass, and the adhesive layer that was in contact with the glass after irradiating light from the adhesive film side has a lower limit of anchor strength to the substrate at 23°C of 0.10N / 25mm. The adhesive film is laminated to glass, and the adhesive layer that was in contact with the glass after irradiating light from the adhesive film side has an anchor strength to the substrate at 23°C of 0.10N / 25mm or more, so that peeling at the interface between the adhesive layer and the substrate can be suppressed, and the handleability of the obtained adhesive film is further improved. The adhesive film is laminated to glass, and the adhesive layer that was in contact with the glass after irradiating light from the adhesive film side has a preferred lower limit of anchor strength to the substrate at 23°C of 0.15N / 25mm. In addition, there is no particular preferred upper limit to the anchoring force of the adhesive layer that was in contact with the glass after the adhesive film was bonded to glass and irradiated with light from the adhesive film side to the substrate at 23°C, but a practical upper limit is approximately 20 N / 25 mm. The anchoring strength of the adhesive layer in contact with the glass after the adhesive film was attached to the glass and irradiated with light from the adhesive film side to the substrate at 23°C was measured by the above-mentioned method for measuring the anchoring strength of the adhesive layer to a substrate at 23°C, in which the adhesive film was attached to the glass and light was irradiated from the surface of the adhesive film not in contact with the glass (for example, wavelength 405 nm, illuminance 80 mW / cm). 2 The adhesive film is then removed from the glass and the anchor strength of the adhesive layer that was in contact with the glass to the substrate at 23°C is measured.
[0105] Methods for adjusting the anchoring strength of the adhesive layer to the substrate at 23°C, the anchoring strength of the adhesive layer to the substrate at 23°C after irradiation with light having a wavelength of 405 nm, and the anchoring strength of the adhesive layer in contact with the glass after laminating the adhesive film to glass and irradiating light from the adhesive film side to the substrate at 23°C include, for example, a method of directly applying an adhesive to the substrate when manufacturing the adhesive film, a method of applying a surface treatment to the substrate such as corona treatment, plasma treatment, sandblasting, chemical etching, or application of a treatment agent (e.g., polyethyleneimine graft polymer, acrylic polymer, polyimide, bismaleimide resin, silane coupling agent, titanium coupling agent, other known adhesion imparting agent, pressure sensitive adhesive, etc.) when manufacturing the adhesive film, a method of adjusting the glass transition temperature (Tg) of the adhesive layer, and adjusting the type and content of a surface conditioner contained in the adhesive layer.
[0106] The adhesive layer has a preferable lower limit of a shear storage modulus of the adhesive layer at 23° C. in an uncured state of 1×10 4 The shear storage modulus of the adhesive layer at 23°C is 1×10 4 The adhesive film obtained has excellent heat resistance when the shear storage modulus is 5×10 Pa or more. 4 Pa, and the more preferable lower limit is 1×10 5 It is Pa. The preferred upper limit of the shear storage modulus of the adhesive layer at 23° C. is 5×10 7 The shear storage modulus of the adhesive layer at 23°C is 5 × 10 7 By setting the shear storage modulus at 23° C. to 3×10 Pa or less, the anchoring force of the adhesive layer to the substrate is improved, and the handleability of the obtained adhesive film is improved. 7 Pa, and more preferably the upper limit is 1×10 7 It is Pa. The shear storage modulus of the adhesive layer at 23° C. can be measured, for example, by dynamic viscoelasticity measurement, etc. Specifically, for example, the adhesive layers are laminated to a thickness of about 1 mm to prepare a measurement sample of only the adhesive layers, and the prepared sample is subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200", etc.) under measurement conditions of shear mode, heating rate of 10° C. / min, measurement temperature of 0° C. to 300° C., and frequency of 10 Hz.
[0107] In the adhesive film of the first aspect of the present invention, the adhesive layer is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 The lower limit of the tensile storage modulus at 23°C after irradiation with light of 405 nm wavelength for 300 seconds (hereinafter, simply referred to as "the tensile storage modulus at 23°C after irradiation with light of 405 nm wavelength of the adhesive layer") is 1.0 x 10 8 The tensile storage modulus of the adhesive layer at 23° C. after curing by irradiation with light having a wavelength of 405 nm is 1.0×10 8 The preferable lower limit of the tensile storage modulus at 23° C. after irradiation of the adhesive layer with light having a wavelength of 405 nm is 1.5×10 8 Pa, more preferably the lower limit is 2.0×10 8 It is Pa. In addition, the preferred upper limit of the tensile storage modulus at 23° C. after irradiation of the adhesive layer with light having a wavelength of 405 nm is 5×10 9 The tensile storage modulus of the adhesive layer at 23° C. after irradiation with light having a wavelength of 405 nm is 5×10 9 By setting the elastic modulus at 23° C. after irradiation with light having a wavelength of 405 nm or less, the adhesive layer has a higher anchoring force with respect to the substrate, and the adhesive film has a higher handleability. 9 Pa, and more preferably the upper limit is 3×10 9 It is Pa. The tensile storage modulus at 23°C after irradiation of the adhesive layer with light having a wavelength of 405 nm was measured by the above-mentioned method for measuring the shear storage modulus at 23°C of the adhesive layer, in which the integrated light intensity of light having a wavelength of 405 nm was 20,000 mJ / cm using an ultra-high pressure mercury lamp. 2 The measured value can be obtained by changing the measurement condition from the shear mode to the tensile mode using a measurement sample irradiated so as to satisfy the following:
[0108] In the adhesive film of the present invention 2, the adhesive layer is attached to glass, and after the adhesive layer is irradiated with light from the adhesive layer side, the lower limit of the tensile storage modulus at 23° C. of the adhesive layer that was in contact with the glass is 1.0×10 8 The adhesive layer was attached to glass, and after light was irradiated from the adhesive layer side, the adhesive layer in contact with the glass had a tensile storage modulus of 1.0 × 10 Pa at 23 ° C. 8 The preferable lower limit of the tensile storage modulus at 23° C. of the adhesive layer in contact with the glass after the adhesive layer is attached to the glass and irradiated with light from the adhesive layer side is 1.5×10 Pa or more. 8 Pa, and a more preferable lower limit is 2.0×10 8 It is Pa. In addition, the adhesive layer is attached to glass, and light is irradiated from the adhesive layer side. After that, the adhesive layer in contact with the glass has a tensile storage modulus at 23° C. of preferably 5×10 9 The adhesive layer was attached to glass, and after light was irradiated from the adhesive layer side, the adhesive layer in contact with the glass had a tensile storage modulus of 5×10 Pa at 23° C. 9 When the adhesive layer is laminated to glass and irradiated with light from the adhesive layer side, the adhesive layer in contact with the glass has a tensile storage modulus at 23° C. of preferably 4×10 Pa or less. 9 Pa, and a more preferable upper limit is 3×10 9 It is Pa. The tensile storage modulus at 23°C of the adhesive layer that was in contact with the glass after the adhesive layer was attached to the glass and irradiated with light from the adhesive layer side was measured by the above-mentioned method for measuring the shear storage modulus at 23°C of the adhesive layer, which was measured by attaching one surface of a measurement sample to glass and irradiating light from the surface of the measurement sample that was not in contact with the glass (for example, wavelength 405 nm, illuminance 80 mW / cm). 2 The measurement can be performed by changing the measurement mode from the shear mode to the tensile mode and using a measurement sample that has been removed from the glass after being irradiated with light of 1000 nm for 300 seconds.
[0109] Methods for adjusting the shear storage modulus of the adhesive layer at 23°C, the tensile storage modulus of the adhesive layer at 23°C after irradiation with light having a wavelength of 405 nm, and the tensile storage modulus of the adhesive layer in contact with glass after laminating the adhesive film to glass and irradiating the adhesive film side with light include, for example, a method of changing the composition of the adhesive layer (e.g., a method of adding an inorganic filler), a method of adjusting the glass transition temperature (Tg) of the adhesive layer, and a method of adjusting the degree of crosslinking of the curable resin.
[0110] The adhesive layer preferably has a glass transition temperature (Tg) in an uncured state greater than 0°C and less than 100°C. When the adhesive layer has a glass transition temperature greater than 0°C, the heat resistance of the resulting adhesive film is improved. When the adhesive layer has a glass transition temperature less than 100°C, the anchoring force of the adhesive layer to the substrate is improved. The adhesive layer's glass transition temperature is more preferably 5°C in lower limit, 95°C in upper limit, 8°C in even more preferred lower limit, and 90°C in even more preferred upper limit. The glass transition temperature of the adhesive layer can be measured, for example, by dynamic viscoelasticity measurement. Specifically, for example, a measurement sample of only the adhesive layer is prepared by laminating the adhesive layers to a thickness of about 1 mm. The obtained measurement sample can be measured as the temperature at which the loss tangent becomes maximum by performing dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200", etc.) under measurement conditions of shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz.
[0111] The adhesive layer is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm 2 The preferred lower limit of the glass transition temperature (Tg) after irradiating the adhesive layer with light having a wavelength of 405 nm for 300 seconds (hereinafter, simply referred to as "glass transition temperature of the adhesive layer after irradiating the adhesive layer with light having a wavelength of 405 nm") is 0°C, and the preferred upper limit is 100°C. When the adhesive layer has a glass transition temperature of 0°C or higher after curing by irradiation with light having a wavelength of 405 nm, the heat resistance of the adhesive film obtained is further improved. When the adhesive layer has a glass transition temperature of 100°C or lower after curing by irradiation with light having a wavelength of 405 nm, the anchoring force of the adhesive layer to the substrate is further improved, and the handleability of the adhesive film obtained is further improved. The more preferred lower limit of the glass transition temperature of the adhesive layer after curing by irradiation with light having a wavelength of 405 nm is 5°C, the more preferred upper limit is 95°C, the even more preferred lower limit is 8°C, and the even more preferred upper limit is 90°C. The glass transition temperature of the adhesive layer after irradiation with light having a wavelength of 405 nm was measured by irradiating a sample adhesive layer obtained by the same method as the above-mentioned method for measuring the glass transition temperature of the adhesive layer with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 This can be obtained by measuring a measurement sample that has been irradiated with light of 1000 nm for 300 seconds.
[0112] Methods for adjusting the glass transition temperature of the adhesive layer and the glass transition temperature of the adhesive layer after curing by irradiation with light having a wavelength of 405 nm include, for example, changing the composition of the adhesive layer (e.g., adding an inorganic filler) and adjusting the degree of crosslinking of the curable resin.
[0113] The adhesive layer preferably has a water absorption rate of 1.0% or less when left to stand for 1 day under conditions of 23°C and 50% RH. When the water absorption rate of the adhesive layer is 1.0% or less, the water absorption rate of the adhesive film obtained can be more easily adjusted to be within the above range. The more preferred upper limit of the water absorption rate of the adhesive layer is 0.9%, and the even more preferred upper limit is 0.8%. Further, although there is no particular preferred lower limit for the water absorption rate of the adhesive layer, the substantial lower limit is about 0.2%. The water absorption rate of the adhesive layer can be measured by the following method. That is, the adhesive layer is cut into a size of 50 mm wide x 50 mm long to prepare a test piece, and then the test piece is dried for 1 hour in an environment of 130 ° C., and the mass W of the test piece immediately after drying is 0 Furthermore, mass W 0 After the measurement, the test piece is left to stand for one day under conditions of 23°C and 50% RH, and the mass W 1 Measure the obtained W 0 , W 1 Using the above, the water absorption rate of the adhesive layer is calculated according to the following formula (I). Water absorption rate (%)={(W 1 -W 0 ) / W 0}×100 (I) (W 0 W: Mass of the test piece immediately after drying for 1 hour under 130℃ 1 (Weight of test piece after leaving it for 1 day under the conditions of 23℃ and 50% RH)
[0114] The adhesive layer was formed by irradiating the adhesive film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2The preferred lower limit of the peak probe tack value at 60° C. after irradiation for 200 seconds so as to obtain a value of 0.30 N / cm 2 After curing, the adhesive layer had a peak probe tack of 0.30 N / cm at 60°C. 2 By virtue of the above, the adhesive film can be more easily peeled off even from an adherend having unevenness by heating during peeling. A more preferable lower limit of the peak value of the probe tack at 60° C. after curing of the adhesive layer is 0.40 N / cm 2 , and a more preferable lower limit is 0.50 N / cm 2 It is. Furthermore, the preferred upper limit of the peak value of the probe tack at 60° C. after the adhesive layer is cured is 5.00 N / cm 2 After curing of the adhesive layer, the peak probe tack value at 60°C is 5.00 N / cm 2 The more preferable upper limit of the peak value of the probe tack at 60° C. after curing of the adhesive layer is 4.00 N / cm or less, so that the adhesive film has appropriate heat resistance. 2 , and more preferably the upper limit is 2.00 N / cm 2 It is. In this specification, the "peak value of probe tack" means the maximum load applied to a probe when the probe is brought into contact with an adhesive layer using a probe tack measuring device and then pulled up, specifically, the peak value of tack measured using a probe tack measuring device under the following measurement conditions: probe diameter 5 mm, pressing speed 0.5 mm / sec, pressing load 98 gf, contact time 10 seconds, and lifting speed 0.1 mm / s. Examples of the above-mentioned probe tack measuring device include a tack tester TAC-2 (manufactured by RHESCA). The specific measurement method is as follows: First, an ultra-high pressure mercury lamp is used, with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2The cured adhesive layer is irradiated for 200 seconds so that the cured adhesive layer is set to 25 mm wide x 50 mm long to prepare a test piece. The test piece thus prepared is then measured using the above-mentioned probe tack measurement device under the above-mentioned measurement conditions in an environment of 60°C and 50% RH to obtain the tack value.
[0115] The adhesive layer was formed by irradiating the adhesive film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The preferred lower limit of the peak probe tack value at 23° C. after irradiation for 200 seconds so as to obtain a value of 0.10 N / cm 2 The adhesive layer has a probe tack value of 0.10 N / cm at 23° C. after curing. 2 By setting the value to the above value, the adhesive strength of the obtained adhesive film at room temperature is further improved. A more preferable lower limit of the peak value of the probe tack at 23° C. after curing of the adhesive layer is 0.20 N / cm 2 , and a more preferable lower limit is 0.25 N / cm 2 It is. Furthermore, the preferred upper limit of the peak value of the probe tack at 23° C. after the adhesive layer is cured is 5.00 N / cm 2 After curing, the adhesive layer had a peak probe tack of 5.00 N / cm at 23°C. 2 The more preferable upper limit of the peak probe tack value at 23° C. after curing of the adhesive layer is 3.00 N / cm 2 , and more preferably the upper limit is 1.00 N / cm 2 It is.
[0116] Methods for adjusting the peak probe tack value at 60°C after curing of the adhesive layer and the peak probe tack value at 23°C after curing of the adhesive layer include, for example, a method for changing the composition in the adhesive layer (for example, a method for including a low molecular weight compound having heat resistance (such as an ultraviolet absorber) in the adhesive layer, a method for changing the surface conditioner, a method for including an inorganic filler, etc.), a method for changing the glass transition temperature of the curable resin, etc.
[0117] The adhesive layer has a thickness of preferably 5 μm at the lower limit and 500 μm at the upper limit. By making the thickness of the adhesive layer within the above range, the water absorption of the adhesive film obtained can be more easily adjusted within the above range. The adhesive layer has a more preferable thickness of 10 μm at the lower limit and 400 μm at the upper limit.
[0118] The adhesive film of the present invention may be a single-sided adhesive film having the adhesive layer on one side of the substrate, or a double-sided adhesive film having the adhesive layer on both sides of the substrate. Among them, from the viewpoint of excellent retention stability in a high-temperature environment, the adhesive film of the present invention is preferably a double-sided adhesive film.
[0119] The method for producing the adhesive film of the present invention is not particularly limited, and it can be produced by using a conventionally known method. Specifically, for example, the above-mentioned curable resin and additives to be blended as necessary are first mixed using a bead mill, ultrasonic dispersion, homogenizer, high-power disperser, roll mill, etc. to prepare an adhesive solution. Next, the obtained adhesive solution is applied to a release PET film and dried at 130°C for 20 minutes to produce a laminated film having an adhesive layer, and two laminated films are produced in total by the same method. Then, the adhesive layers of the laminated film are stacked on both sides of the substrate so as to face each other, and the laminated film is aged for 24 hours under an environment of 23°C and 50% RH, thereby producing a double-sided adhesive film. The aging process can be omitted.
[0120] When producing an adhesive film, it is preferable to directly apply an adhesive solution to a substrate to form an adhesive layer. By directly applying an adhesive solution to a substrate to form an adhesive layer, the adhesive layer and the substrate have improved adhesion, so that the adhesive layer has improved anchoring power to the substrate at 23°C, and the adhesive film obtained has improved handling properties.
[0121] When producing the adhesive film, it is preferable to subject the substrate to a surface treatment before use. By subjecting the substrate to a surface treatment, the anchoring force of the adhesive layer to the substrate at 23° C. is improved, and the handleability of the resulting adhesive film is improved. Examples of the surface treatment include corona treatment, plasma treatment, sandblasting, chemical etching, and application of a treatment agent (e.g., polyethyleneimine graft polymer, acrylic polymer, polyimide, bismaleimide resin, silane coupling agent, titanium coupling agent, other known adhesion imparting agent, adhesive, etc.), among which corona treatment is preferred from the viewpoint of easy surface treatment. Examples of the method of corona treatment include corona treatment of the substrate using a high-frequency power supply device (manufactured by Kasuga Electric Co., Ltd., "AGI-020", etc.) under conditions of output of 0.3 kW, electrode distance of 1 mm, and speed of 2 m / min. Alternatively, a commercially available product having a substrate subjected to a corona treatment may be used.
[0122] When producing the adhesive film, it is preferable to dry the substrate before use. By drying the substrate before use, the moisture content of the substrate of the obtained adhesive film is reduced, so that the occurrence of foaming in a high-temperature environment can be more suppressed. Therefore, the heat resistance of the obtained adhesive film is further improved, and the obtained adhesive film can be more suppressed from peeling off in a high-temperature environment. The conditions for the drying treatment include, for example, placing the adhesive film in an oven preheated to 130° C. and heating for 30 minutes, or leaving it to stand for 10 minutes in an environment of 130° C. and 50% RH, etc. In the drying treatment of the substrate described above, the substrate alone may be placed in the oven and dried, or a laminate of the substrate and the adhesive layer may be placed in the oven and dried.
[0123] The adhesive film of the present invention has a preferred lower limit of 10% light transmittance at a wavelength of 405 nm. The light transmittance of 10% or more allows a sufficient amount of light to be irradiated onto the adhesive layer, so that the adhesive layer of the adhesive film can be sufficiently cured. The more preferred lower limit of the light transmittance is 15%. The preferred upper limit of the light transmittance is 98%. The light transmittance of 98% or less can prevent the adherend from being irradiated with light when the adhesive film is irradiated with light, so that the adhesive film can be peeled off while preventing deterioration of the quality of the adherend. The more preferred upper limit of the light transmittance is 95%.
[0124] The adhesive film of the present invention has a preferred lower limit of the total thickness of 10 μm and a preferred upper limit of 700 μm. When the adhesive film of the present invention has a total thickness of 10 μm or more, the adhesive film can have sufficient pressure-sensitive or heat-sensitive adhesive strength at the beginning. When the adhesive film has a total thickness of 700 μm or less, the adhesive film can exhibit high flexibility, exhibit high conformability to an adherend having unevenness, and can be easily peeled off at the time of peeling. The more preferred lower limit of the total thickness of the adhesive film is 13 μm, the even more preferred lower limit is 15 μm, the more preferred upper limit is 580 μm, and the even more preferred upper limit is 550 μm.
[0125] The adhesive film of the present invention is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2The preferred lower limit of the 5% weight loss temperature after 200 seconds of irradiation so as to obtain a temperature (hereinafter, sometimes simply referred to as "5% weight loss temperature after curing the adhesive layer of the adhesive film of the present invention") is 390°C. When the 5% weight loss temperature after curing the adhesive layer of the adhesive film of the present invention is 390°C or higher, the adhesive film of the present invention has better heat resistance. A more preferred lower limit of the 5% weight loss temperature after curing the adhesive layer of the adhesive film of the present invention is 400°C, and an even more preferred lower limit is 420°C. Further, there is no particular upper limit to the 5% weight loss temperature after the adhesive layer of the adhesive film of the present invention is cured, but the practical upper limit is about 600°C. The 5% weight loss temperature after the adhesive layer of the adhesive film of the present invention is cured can be measured by simultaneous differential thermal and thermogravimetry. Specifically, it can be measured by, for example, the following method. That is, the adhesive film is cut into a size of 25 mm wide x 50 mm long to prepare a test piece. The obtained test piece is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer is cured by irradiating for 200 seconds so that the adhesive layer is cured. The test piece with the cured adhesive layer is weighed in an aluminum pan, and the aluminum pan is set in a differential thermal-thermogravimetric simultaneous measuring device. When the temperature is raised from 30°C to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, the temperature at the point when the mass of the adhesive film is reduced by 5% compared to the mass before the temperature rise can be obtained as the 5% weight loss temperature. As the differential thermal-thermogravimetric simultaneous measuring device, for example, STA7200RV (manufactured by Hitachi High-Tech Science Corporation) can be used. Note that the test piece is not laminated with a release PET film to protect the adhesive layer.
[0126] Methods for adjusting the 5% weight loss temperature after curing of the adhesive layer of the adhesive film of the present invention to within the above-mentioned range include, for example, changing the composition of the adhesive layer (e.g., by incorporating an inorganic filler) and changing the type of substrate.
[0127] The adhesive film of the present invention has a preferred lower limit of 10% weight loss temperature of 400° C. When the adhesive film has a 10% weight loss temperature of 400° C. or higher, the adhesive film of the present invention has better heat resistance. The more preferred lower limit of the 10% weight loss temperature of the adhesive film of the present invention is 410° C., the even more preferred lower limit is 420° C., the even more preferred lower limit is 425° C., the particularly preferred lower limit is 440° C., and the especially preferred lower limit is 450° C. Further, there is no particular preferred upper limit to the 10% weight loss temperature of the adhesive film of the present invention, but the substantial upper limit is about 600°C. The 10% weight loss temperature of the adhesive film of the present invention can be measured by a simultaneous differential thermal / thermogravimetric analyzer. Specifically, it can be measured by the following method. That is, the adhesive film is cut into a size of φ4 mm to prepare a test piece. The obtained test piece is weighed in an aluminum pan, and the aluminum pan is set in a differential thermal-thermogravimetric simultaneous measuring device. When the temperature is increased from 30°C to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, the temperature at which the mass of the adhesive film decreases by 10% compared to before the temperature increase can be obtained as the 10% weight loss temperature. As the differential thermal-thermogravimetric simultaneous measuring device, for example, STA7200RV (manufactured by Hitachi High-Tech Science Corporation) can be used. Note that the test piece is not laminated with a release PET film to protect the adhesive layer.
[0128] Methods for adjusting the 10% weight loss temperature to within the above-mentioned range include, for example, changing the composition of the adhesive layer, changing the type of substrate, and adjusting the glass transition temperature (Tg) of the curable resin contained in the adhesive layer.
[0129] The adhesive film of the present invention has a water absorption rate (hereinafter, sometimes simply referred to as "water absorption rate of the adhesive film") of 0.60% when left to stand for 1 day under conditions of 23°C and 50% RH. When the water absorption rate of the adhesive film is 0.60% or less, foaming that occurs between the layers of the film during high-temperature processing can be suppressed, and therefore, peeling of the adhesive film of the present invention during high-temperature processing can be prevented. Further, although there is no particular lower limit for the water absorption rate of the adhesive film, the substantial lower limit is about 0.10%. The water absorption rate of the adhesive film of the present invention can be measured by the same method as that for the water absorption rate of the adhesive layer described above.
[0130] Methods for adjusting the water absorption rate of the adhesive film to within the above-mentioned range include, for example, changing the composition of the adhesive layer, changing the type of substrate, using a substrate that has been dried during the production of the adhesive film, changing the ratio of the thickness of the substrate to the overall thickness of the film, and drying the adhesive solution on the substrate to dry the adhesive solvent and dry the substrate at the same time.
[0131] The adhesive film of the present invention has high heat resistance and excellent handleability, and therefore can be suitably used for fixing components to an adherend exposed to high temperatures, particularly for fixing electronic components in electronic devices exposed to high temperature environments for long periods of time. It can also be suitably used for protection and temporary fixation of adherends that undergo high-temperature processing at 300° C. or higher. For example, during processing of electronic components such as semiconductors, in order to facilitate handling of the electronic components and prevent damage to the electronic components, the adhesive film can be suitably used for temporarily fixing the electronic components to a support plate via the adhesive film or for protecting the electronic components by attaching the adhesive film to the electronic components. In particular, the adhesive film can be suitably used for temporary fixation of electronic components. The high-temperature processing includes, for example, heat resistance treatment of semiconductors.
[0132] The present invention also relates to a method for producing an adhesive film having an adhesive layer and a substrate, the adhesive layer containing a photocurable adhesive, the adhesive film being laminated to glass and the adhesive layer in contact with the glass having an anchor strength to the substrate at 23°C of 0.10 N / 25 mm or more after irradiating light from the adhesive film side, the method including a step of directly applying the adhesive layer to the substrate. The method for producing an adhesive film of the present invention can produce an adhesive film that has both high heat resistance and excellent handleability.
[0133] The method for producing an adhesive film of the present invention includes a step of directly applying an adhesive to a substrate. By including a step of directly applying an adhesive to a substrate, the adhesive film production method of the present invention further improves the adhesion between the adhesive layer and the substrate, and therefore the adhesive film obtained is laminated to glass, and after irradiating light from the adhesive film side, the adhesive layer in contact with the glass has improved anchoring power to the substrate at 23°C, resulting in the adhesive film obtained having excellent handleability.
[0134] The method for producing an adhesive film of the present invention preferably includes a step of performing a surface treatment on at least one side of the substrate. By including a step of performing a surface treatment on the substrate, the adhesion between the adhesive layer and the substrate is further improved, so that the adhesive film obtained has a further improved anchoring force of the adhesive layer to the substrate at 23°C and has better handling properties. Examples of the surface treatment in the method for producing an adhesive film of the present invention include corona treatment, plasma treatment, sandblasting, chemical etching, and treatment agent application (e.g., polyethyleneimine graft polymer, acrylic polymer, polyimide, bismaleimide resin, silane coupling agent, titanium coupling agent, other known adhesion imparting agents, pressure sensitive adhesives, etc.). That is, the method for producing an adhesive film of the present invention preferably includes a step of performing at least one type of surface treatment selected from the group consisting of corona treatment, plasma treatment, sandblasting, chemical etching, and treatment agent application on at least one surface of the substrate, and among these, it is preferable to include a step of performing corona treatment from the viewpoint of easily performing the surface treatment. As a method of performing corona treatment, for example, a high-frequency power supply device (such as "AGI-020" manufactured by Kasuga Electric Co., Ltd.) may be used to perform corona treatment on the substrate under conditions of an output of 0.3 kW, an electrode distance of 1 mm, and a speed of 2 m / min. Furthermore, a commercially available product that has been subjected to a corona treatment may be used as the substrate.
[0135] The method for producing an adhesive film of the present invention preferably includes a step of drying the substrate. By including the step of drying the substrate, the moisture content of the substrate of the obtained adhesive film is reduced, so that the generation of foaming in a high-temperature environment can be further suppressed, and the heat resistance of the obtained adhesive film is further improved, and the obtained adhesive film can be further suppressed from peeling off in a high-temperature environment. The conditions for the drying treatment in the method for producing an adhesive film of the present invention include, for example, placing the adhesive film in an oven preheated to 130° C. and heating for 30 minutes, or leaving it to stand for 10 minutes in an environment of 130° C. and 50% RH, etc. In the drying treatment of the substrate described above, the substrate alone may be placed in an oven and dried, or a laminate of the substrate and the adhesive layer may be placed in an oven and dried.
[0136] The adhesive film produced by the method for producing an adhesive film of the present invention has both high heat resistance and excellent handling properties, and is therefore suitable for use in fixing components to adherends exposed to high temperatures, particularly in fixing electronic components in electronic devices exposed to high-temperature environments for long periods of time. The obtained adhesive film can be suitably used for protecting and temporarily fixing adherends that undergo high-temperature processing at 300° C. or higher. For example, during processing of electronic components such as semiconductors, the adhesive film can be suitably used to temporarily fix electronic components to a support plate via the adhesive film or to protect electronic components by attaching the adhesive film to the electronic components in order to facilitate handling of the electronic components and prevent them from being damaged. In particular, the adhesive film can be suitably used for temporarily fixing electronic components.
[0137] Examples of adhesive films that can be produced by the method for producing an adhesive film of the present invention include the adhesive film of the present invention described above. Effect of the Invention
[0138] According to the present invention, it is possible to provide an adhesive film that can achieve both high heat resistance and excellent handleability. Also, according to the present invention, it is possible to provide a method for producing an adhesive film that can achieve both high heat resistance and excellent handleability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0139] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0140] (Synthesis of polyimide compounds 1-A, 2-A, and 3-A) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075") and 39 g (0.0765 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a brown solid resin (polyimide compounds 1-A, 2-A, and 3-A) having a constitutional unit represented by the following formula (6), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained. The weight average molecular weight of the obtained polyimide compound was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 × 150 mm (manufactured by Waters Corporation) as a column, and was found to be 90,000.
[0141] [ka]
[0142] (Synthesis of polyimide compounds 1-C and 2-C) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075") and 23.732 g (0.0765 mol) of 4,4'-oxydiphthalic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a brown solid resin (polyimide compound 1-C, 2-C) having a constitutional unit represented by the following formula (7), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained. The weight average molecular weight of the obtained polyimide compound was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 × 150 mm (manufactured by Waters Corporation) as a column, and was found to be 110,000.
[0143] [ka]
[0144] (Synthesis of polyimide compound 1-D) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075"), 31.2 g (0.0612 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, and 3.335 g (0.0153 mol) of pyromellitic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a resin (polyimide compound 1-D) having structural units represented by the following formulas (8-1) and (8-2), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained as a brown solid. The weight average molecular weight of the obtained polyimide compound 1-D was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 × 150 mm (manufactured by Waters Corporation) as a column, and was found to be 100,000.
[0145] [ka]
[0146] (Synthesis of polyimide compound 1-E) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 39.9 g (0.075 mol) of dimer diamine (manufactured by Croda, "Priamine 1075"), 11.7 g (0.0230 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, and 11.674 g (0.0536 mol) of pyromellitic anhydride were added in this order. A degassing tube and a condenser were attached to the flask, and the resulting mixture was refluxed for 6 hours and cooled to room temperature. A toluene solution of a resin (polyimide compound 1-E) having structural units represented by the following formulas (9-1) and (9-2), no maleimide group, and an imide skeleton in the repeating unit of the main chain was obtained as a brown solid. The weight average molecular weight of the obtained polyimide compound 1-E was measured by gel permeation chromatography (GPC, apparatus name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 × 150 mm (manufactured by Waters Corporation) as a column, and was found to be 98,000.
[0147] [ka]
[0148] (Synthesis of bismaleimide compound 1-F) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon (registered trademark) stirrer. 56 g (0.1 mol) of dimer diamine (Croda, Priamine 1075) and 19.6 g (0.2 mol) of maleic anhydride were added, followed by 5 g of methanesulfonic anhydride. The resulting solution was refluxed for 12 hours, cooled to room temperature, and 300 mL of toluene was added to the flask. The solution was allowed to stand for layer separation, and the lower layer, which was an impurity, was removed. The resulting solution was filtered through a glass frit funnel filled with silica gel, and the solvent was removed under vacuum to obtain a bismaleimide compound 1-F represented by the following formula (10) in the form of a brown liquid.
[0149] [ka]
[0150] (Synthesis of acrylic copolymer 1-G) A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared, and 93 parts by mass of 2-ethylhexyl acrylate, 1 part by mass of acrylic acid, 6 parts by mass of hydroxyethyl methacrylate, 0.01 parts by mass of lauryl mercaptan, and 80 parts by mass of ethyl acetate were added to the reactor, and the reactor was heated to start reflux. Subsequently, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added as a polymerization initiator to start polymerization under reflux. Next, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added one hour and two hours after the start of polymerization, and further 0.05 parts by mass of t-hexylperoxypivalate was added four hours after the start of polymerization to continue the polymerization reaction. Then, 8 hours after the start of polymerization, an ethyl acetate solution containing a functional group-containing (meth)acrylic polymer with a solid content of 55% by mass and a weight average molecular weight of 600,000 was obtained. 3.5 parts by mass of 2-isocyanatoethyl methacrylate was added to 100 parts by mass of the resin solid content of the ethyl acetate solution containing the obtained functional group-containing (meth)acrylic polymer and reacted to obtain an acrylic copolymer (acrylic copolymer 1-G) having a weight-average molecular weight of 800,000 and double bonds in the side chains. The weight average molecular weight of the obtained acrylic copolymer 1-G was measured by gel permeation chromatography (GPC) using THF as an eluent and HR-MB-M (product name, manufactured by Waters Corporation) as a column.
[0151] (Synthesis of acrylic copolymer 1-H) Regarding the above-mentioned "(Synthesis of Acrylic Copolymer 1-G)", except that a monomer mixture containing 70 parts by mass of ethyl acrylate and 23 parts by mass of methyl methacrylate was used instead of 93 parts by mass of 2-ethylhexyl acrylate, the same method as for the synthesis of Acrylic Copolymer 1-G was used to synthesize Acrylic Copolymer 1-H, and the weight average molecular weight was measured. The weight average molecular weight of Acrylic Copolymer 1-H was 500,000.
[0152] (Synthesis of acrylic copolymer 2-E) A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared, and 94 parts by mass of 2-ethylhexyl acrylate, 6 parts by mass of hydroxyethyl methacrylate, 0.01 parts by mass of lauryl mercaptan, and 80 parts by mass of ethyl acetate were added to the reactor, and the reactor was heated to start reflux. Subsequently, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added as a polymerization initiator to start polymerization under reflux. Next, 0.01 parts by mass of 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane was added one hour and two hours after the start of polymerization, and further, 0.05 parts by mass of t-hexylperoxypivalate was added four hours after the start of polymerization to continue the polymerization reaction. Then, 8 hours after the start of polymerization, an ethyl acetate solution containing a functional group-containing acrylic polymer with a solid content of 55% by mass and a weight average molecular weight of 500,000 was obtained. 3.5 parts by mass of 2-isocyanatoethyl methacrylate was added to 100 parts by mass of the resin solid content of the ethyl acetate solution containing the obtained functional group-containing acrylic polymer and reacted to obtain acrylic copolymer 2-E. The weight average molecular weight of the acrylic copolymer 2-E was 550,000. The weight average molecular weight of the obtained acrylic copolymer 2-E was measured by gel permeation chromatography (GPC, device name: Acquity APC system (manufactured by Waters Corporation)) using THF as an eluent and an HR-MB-M 6.0 x 150 mm (manufactured by Waters Corporation) as a column.
[0153] (Preparation of adhesive film) (Example 1-1) Each of the materials listed in Table 1 was added to 150 mL of toluene and mixed to prepare an adhesive solution. The polyimide compound B is a polyimide compound having a maleimide group represented by the following formula (11) (manufactured by Designer Molecules, "BMI-3000GEL"). The obtained adhesive solution was applied with a doctor knife onto the release-treated surface of a 50 μm-thick PET film (release PET film) prepared as a separator, with one side subjected to release treatment, so that the dried thickness was as shown in Table 1. The coating solution was dried by heating at 130° C. for 10 minutes to obtain a laminated film having an adhesive layer. Another laminated film was also produced by the same method. The laminated film was laminated on one side and the other side of a substrate of the type and thickness shown in Table 1 so that the adhesive layer faced the substrate, and the substrate was aged for 1 hour in an environment of 23° C. to obtain an adhesive film having an adhesive layer on both sides of the substrate.
[0154] [ka]
[0155] In formula (11), n is the number of repetitions.
[0156] (Measurement of shear storage modulus of adhesive layer (uncured state) at 23°C) The obtained adhesive layers were stacked to a thickness of about 1 mm to prepare a measurement sample of only the adhesive layer. The prepared measurement sample was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") under the measurement conditions of shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz, to measure the shear storage modulus (Pa) of the adhesive layer (uncured state) at 23°C. The results are shown in Table 1.
[0157] (Measurement of tensile storage modulus at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) Before setting the obtained measurement sample in the dynamic viscoelasticity measuring device, the adhesive layer was irradiated with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illumination intensity of 80 mW / cm 2 The tensile storage modulus (Pa) at 23°C after irradiation of the adhesive layer with light of a wavelength of 405 nm was obtained in the same manner as in "Measurement of the shear storage modulus of the adhesive layer (uncured state) at 23°C" above, except that a measurement sample was used that had been irradiated with light of a wavelength of 405 nm for 300 seconds, and that the dynamic viscoelasticity measurement was performed in tension mode instead of shear mode. The results are shown in Table 1.
[0158] (The adhesive layer was attached to glass, and light was irradiated from the adhesive layer side, after which the tensile storage modulus at 23°C of the adhesive layer that was in contact with the glass was measured.) One surface of the measurement sample obtained in the above-mentioned "(Measurement of the shear storage modulus of the adhesive layer (uncured state) at 23°C)" was attached to glass, and the surface of the measurement sample not in contact with the glass was exposed to light with a wavelength of 405 nm and an illuminance of 80 mW / cm 2 The adhesive layer was attached to glass, and the tensile storage modulus (Pa) of the adhesive layer in contact with the glass after being irradiated with light from the adhesive layer side was obtained at 23°C by the same method as in "(Measurement of the shear storage modulus of the adhesive layer (uncured state) at 23°C)" described above, except that the measurement sample was removed from the glass after being irradiated with light for 300 seconds, and the measurement was performed in tension mode instead of shear mode in the dynamic viscoelasticity measurement. The results are shown in Table 1.
[0159] (Measurement of anchor strength of adhesive layer (uncured state) to substrate at 23°C) One side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") was attached to a SUS plate that had been washed with ethanol and then wiped dry, and the adhesive layer of the obtained adhesive film that was not to be measured was then superimposed on the other side of the double-sided tape, with the adhesive layer of the adhesive film to be measured facing up. Furthermore, a 25 mm wide silicon tape (manufactured by Sliontec Co., Ltd., "6260-01") was pressed against the exposed adhesive layer of the adhesive film to be measured by moving a 2 kg hand roller back and forth once at a speed of 10 mm / min. A 25 mm wide cut was made along the silicon tape in the adhesive layer pressed against the silicon tape, and the test sample was prepared by curing at 23°C and 50% RH for 1 hour. The obtained test samples were subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300mm / min using a tensile tester (Shimadzu Corporation, "Autograph AGS-X") in accordance with JIS Z0237. The adhesive layer pressed onto the silicon tape was peeled off from the substrate to measure the 90° peel strength (N / 25mm) of the adhesive layer against the substrate. The obtained 90° peel strength was taken as the anchor strength of the adhesive layer (uncured state) against the substrate at 23°C. The results are shown in Table 1.
[0160] (Measurement of anchoring strength to substrate at 23°C after irradiating adhesive layer with light of 405 nm wavelength) Before attaching one side of a commercially available double-sided tape to a SUS plate that had been washed with ethanol and then wiped dry, the adhesive film was irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm 2 The anchoring strength (N / 25 mm) of the adhesive layer to the substrate at 23°C after irradiation with light of a wavelength of 405 nm was measured in the same manner as in "(Measurement of anchoring strength of adhesive layer (uncured state) to substrate at 23°C)" above, except that the adhesive film was irradiated with light of a wavelength of 405 nm for 300 seconds. The results are shown in Table 1.
[0161] (An adhesive film was attached to glass, and light was irradiated from the adhesive film side. Then, the anchoring strength of the adhesive layer that was in contact with the glass was measured at 23°C against the substrate.) The adhesive film was attached to the glass, and the surface of the adhesive film not in contact with the glass was irradiated with a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 The adhesive film of the adhesive layer was attached to glass, and the adhesive film was irradiated with light from the adhesive film side for 300 seconds, and then the adhesive film removed from the glass was used to measure the 90° peel strength of the adhesive layer that was in contact with the glass to the substrate. The same method as in "(Measurement of anchor strength of adhesive layer (uncured state) to substrate at 23°C)" was used to measure the anchor strength (N / 25mm) of the adhesive layer that was in contact with the glass to the substrate at 23°C. The results are shown in Table 1.
[0162] (Measurement of glass transition temperature of adhesive layer (uncured state)) Measurement samples were prepared using the same method as described above in "(Measurement of shear storage modulus of adhesive layer (uncured state) at 23°C)". The obtained measurement samples were subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") under the following measurement conditions: shear mode, heating rate of 10°C / min, measurement temperature of 0°C to 300°C, and frequency of 10 Hz, to measure the glass transition temperature (°C) of the adhesive layer (uncured state). The results are shown in Table 1.
[0163] (Measurement of glass transition temperature of substrate) For the substrates shown in Table 1, dynamic viscoelasticity measurements were performed using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") under the measurement conditions of tensile mode, heating rate of 10°C / min, measurement temperature of 0°C to 400°C, and frequency of 10 Hz, to measure the glass transition temperature (°C) of the substrates. The results are shown in Table 1.
[0164] (Measurement of the melting point of the base material) For the substrates shown in Table 1, differential scanning calorimetry (DSC) was performed under the measurement conditions of a nitrogen atmosphere, a heating rate of 10°C / min, and a measurement temperature of 30°C to 500°C, using a differential scanning calorimetry (DSC) device (Hitachi High-Tech Science Corporation, "DSC-7020"). From the obtained differential scanning calorimetry curve, the temperature showing the endothermic peak was taken as the melting point (°C) of the substrate. The results are shown in Table 1.
[0165] (Measurement of peak probe tack value after adhesive layer curing) (1) Peak probe tack value at 23°C An ultra-high pressure mercury lamp was used from one adhesive layer side (the adhesive layer side not being measured) with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating the adhesive layer for 200 seconds so that the adhesive layer was cured, and the adhesive layer on the side not irradiated with light was cut into a size of 25 mm wide x 50 mm long to prepare a test piece. The prepared test piece was measured using a probe tack measuring device (manufactured by RHESCA, "Tacking Tester TAC1000") under the measurement conditions of 23°C, humidity 50%, probe diameter 5 mm, pressing speed 0.5 mm / sec, pressing load 98 gf, contact time 10 seconds, and lifting speed 0.1 mm / s to measure the peak probe tack value at 23°C. The results are shown in Table 1.
[0166] (2) Peak probe tack value at 60°C The peak probe tack value at 60° C. was measured in the same manner as in the above-mentioned “(1) Peak probe tack value at 23° C.,” except that the measurement temperature was changed from 23° C. to 60° C. The results are shown in Table 1.
[0167] (Measurement of 5% weight loss temperature after curing the adhesive layer of the adhesive film) The obtained adhesive film was cut into a size of 25 mm wide x 50 mm long to prepare a test piece, and the obtained test piece was irradiated with a 405 nm wavelength ultra-high pressure mercury lamp at an illuminance of 100 mW / cm from one adhesive layer side. 2 The accumulated light intensity is 20,000 mJ / cm 2The adhesive layer was cured by irradiating for 200 seconds so that the adhesive layer was cured. The test piece with the cured adhesive layer was weighed in an aluminum pan, and the aluminum pan was set in a differential thermal-thermogravimetric simultaneous measurement device (Hitachi High-Tech Science Corporation, "STA7200RV"), and the temperature was raised from 30°C to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere. The temperature at which the mass of the adhesive film decreased by 5% compared to the mass before heating was determined as the 5% weight loss temperature. Note that the test piece was not laminated with a release PET film to protect the adhesive layer. The results are shown in Table 1.
[0168] (Measurement of 10% weight loss temperature of adhesive film) Each adhesive film obtained was cut into a size of 5 mm wide x 10 mm long to prepare a test piece. The obtained test piece was weighed into an aluminum pan, and the aluminum pan was set in a differential thermal-thermogravimetric simultaneous measurement device (Hitachi High-Tech Science Corporation, "STA7200RV"), and the temperature was raised at a heating rate of 10°C / min in a temperature range from 30°C to 500°C under a nitrogen atmosphere. The temperature at which the mass of the adhesive film decreased by 10% compared to the mass before heating was taken as the 10% weight loss temperature (°C). Note that the test piece was not laminated with a release PET film to protect the adhesive layer. The results are shown in Table 1.
[0169] (Measurement of water absorption rate of adhesive film when left for one day under conditions of 23℃ and 50% RH) The obtained adhesive film was cut into a size of 20 mm wide x 50 mm long to prepare a test piece, which was then dried for 1 hour under an environment of 130°C and 50% RH. The mass W 0 Furthermore, the mass W 0 After the measurement, the test piece is left to stand for one day under conditions of 23°C and 50% RH, and the mass W 1 The obtained W 0 , W 1 Using the above, the water absorption rate (%) of the adhesive film when left to stand for one day under the conditions of 23°C and 50% RH was calculated according to the following formula (I). Note that no release PET film for protecting the adhesive layer was laminated on the test piece. The results are shown in Table 1. Water absorption rate (%)={(W 1 -W 0 ) / W 0}×100 (I) (W 0 W: Mass of the test piece immediately after drying for 1 hour under 130℃ and 50% RH 1 (Weight of test piece after leaving it for 1 day under the conditions of 23℃ and 50% RH)
[0170] (Example 1-2) In the above-mentioned "(Preparation of adhesive film)", an adhesive film was prepared, and measurements and evaluations were performed in the same manner as in Example 1-1, except that a substrate having a surface subjected to corona treatment shown in Table 1 was used under the conditions of an output of 0.3 kW, an electrode distance of 1 mm, and a speed of 2 m / min using a high-frequency power supply device (manufactured by Kasuga Electric Co., Ltd., "AGI-020"). The results are shown in Table 1.
[0171] (Examples 1-3 and 1-7) An adhesive solution was prepared in the same manner as in "(Preparation of adhesive film)" above. The prepared adhesive solution was directly applied to one side of the substrate shown in Table 1 so that the dry thickness was 50 μm, and the substrate was dried at 130° C. for 10 minutes to form an adhesive layer, and then the release-treated surface of a release PET film was laminated so as to face the adhesive layer. An adhesive layer prepared in the same manner was also laminated on the other side of the substrate, and the substrate was aged at 23° C. for 1 hour to obtain an adhesive film having adhesive layers on both sides of the substrate. The measurements and evaluations were carried out in the same manner as in Example 1-1, except for the method for producing the adhesive film. The results are shown in Table 1.
[0172] (Examples 1-4 to 1-6, 1-8, 1-10 to 1-11, Comparative Examples 1-1 to 1-5) In the above "(Preparation of adhesive film)", adhesive films were prepared and measurements and evaluations were performed in the same manner as in Example 1-1, except that the type of substrate and the composition of the adhesive layer were changed as shown in Tables 1 and 2. The results are shown in Tables 1 and 2.
[0173] (Examples 1 to 9) (Preparation of adhesive film) An adhesive film having an adhesive layer only on one side of the substrate was obtained in the same manner as in Example 1-1, except that a laminate film was laminated only on one side of the substrate.
[0174] (Measurement of anchor strength of adhesive layer (uncured state) to substrate at 23°C) One side of a commercially available double-sided tape (manufactured by Sekisui Chemical Co., Ltd., "3810H") was attached to a SUS plate that had been washed with ethanol and then wiped dry, and the other side of the double-sided tape was placed on top of the substrate side of the adhesive film of Example 1-9 that did not have an adhesive layer, with the adhesive layer of the adhesive film to be measured facing up. Furthermore, a 25 mm wide silicon tape (manufactured by Sliontec Co., Ltd., "6260-01") was pressed against the exposed adhesive layer of the adhesive film by moving a 2 kg hand roller back and forth once at a speed of 10 mm / min. A 25 mm wide cut was made along the silicon tape in the adhesive layer pressed against the silicon tape, and the test sample was prepared by curing at 23°C and 50% RH for 1 hour. The obtained test samples were subjected to a 90° peel test at 23°C, 50% RH, and a peel speed of 300 mm / min using a tensile tester (Shimadzu Corporation, "Autograph AGS-X") in accordance with JIS Z0237, and the adhesive layer pressed onto the silicon tape was peeled off from the substrate to measure the anchor strength of the adhesive layer (uncured state) to the substrate at 23°C. The results are shown in Table 1.
[0175] The abbreviations for the resins contained in the base materials and the types of base materials shown in Tables 1 and 2 are as follows. PEEK: Polyetheretherketone PET: Polyethylene terephthalate PEN: Polyethylene naphthalate LDPE: Low density polyethylene PEEK-containing substrate: EXPEEK (Kurabo Industries, Ltd.) Polyimide-containing substrate: Upilex 25U (manufactured by UBE) Polyamide-containing base material: Uniamide EX-25 (manufactured by Unitika Ltd.) PET film: Lumirror S-10 (manufactured by Toray Industries, Inc.) PEN-containing base material: Teonex Q83C (manufactured by Toyobo Co., Ltd.) LDPE-containing substrate: LLDPE film A-1 (manufactured by Tamapoly)
[0176] [Table 1]
[0177] [Table 2]
[0178] (Examples 2-1 to 2-2, 2-4 to 2-6, Comparative Examples 2-1 to 2-2) (Preparation of adhesive film) Each material shown in Table 3 was added to 150 mL of toluene and mixed to prepare a solution containing an adhesive resin composition. Note that polyimide compound 2-B is a polyimide compound having a maleimide group represented by the above formula (11) (manufactured by Designer Molecules, "BMI-3000GEL"), and bismaleimide compound 2-D is a bismaleimide compound represented by the above formula (10) (manufactured by Designer Molecules, "BMI-689"). The solution containing the prepared adhesive resin composition was applied with a doctor knife to the release-treated surface of a 50 μm-thick PET film (release PET film) prepared as a separator, which had been subjected to release treatment on one side, so that the dried thickness was as shown in Table 3. The coating solution was dried by heating at 130 ° C. for 10 minutes to prepare a laminated film (a) having an adhesive layer 1. The obtained laminated film (a) was laminated on one side of the substrate shown in Table 3 so as to face the adhesive layer. A laminated film (b) having an adhesive layer 2 having the composition and thickness shown in Table 3 was prepared by the same method, and the laminated film (b) was laminated on the other side of the substrate so as to face the adhesive layer, thereby obtaining an adhesive film having an adhesive layer on both sides of the substrate. In addition, for Comparative Examples 2-1 and 2-2 having an adhesive layer containing a crosslinking agent, the laminated film (a) and the laminated film (b) were laminated on the substrate, and then the substrate was further aged at 40 ° C. for 3 days to obtain an adhesive film having an adhesive layer on both sides of the substrate. In the evaluation described below, the adhesive layer 1 was used as the adhesive layer for adhering to a wafer.
[0179] (Measurement of peak probe tack value after adhesive layer curing) From the adhesive layer 2 side, an ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating for 200 seconds so that the adhesive layer was cured. Otherwise, the same procedure as in Example 1-1 was followed to measure the peak probe tack value at 23°C after the adhesive layer was cured, and the peak probe tack value at 60°C after the adhesive layer was cured. The results are shown in Table 3.
[0180] (Measurement of 5% weight loss temperature after curing the adhesive layer of the adhesive film) From the adhesive layer 2 side, an ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating for 200 seconds so that the temperature at which the adhesive layer of the adhesive film lost 5% of its weight was measured after the adhesive layer was cured in the same manner as in Example 1-1. The results are shown in Table 3.
[0181] (Measurement of 10% weight loss temperature of adhesive film) The adhesive film was measured for 10% weight loss temperature in the same manner as in Example 1-1. The results are shown in Table 3.
[0182] (Measurement of tensile storage modulus at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) The laminate, in which the adhesive layer 1 is layered to a thickness of 1 mm, is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm 2 The accumulated light intensity is 20,000 mJ / cm 2 The measurement sample was irradiated for 200 seconds so that the tensile storage modulus was measured at 23° C. after irradiating the adhesive layer with light having a wavelength of 405 nm in the same manner as in Example 1-1. The results are shown in Table 3.
[0183] (Measurement of anchoring strength to substrate at 23°C after irradiating adhesive layer with light of 405 nm wavelength) The adhesive film was irradiated from the adhesive layer 2 side with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm 2 An adhesive film was prepared by irradiating the adhesive layer with light having a wavelength of 405 nm for 300 seconds. Otherwise, the same procedure as in Example 1-1 was followed to measure the anchoring strength of the adhesive layer to the substrate at 23° C. after irradiation with light having a wavelength of 405 nm. The results are shown in Table 3.
[0184] (Measurement of water absorption rate of adhesive film when left for one day under conditions of 23℃ and 50% RH) In the same manner as in Example 1-1, the water absorption rate of the adhesive film was measured after it was left to stand for one day under conditions of 23° C. and 50% RH. The results are shown in Table 3.
[0185] (Example 2-3) In the above-mentioned "(Measurement of peak value of probe tack after curing of adhesive layer)" and "(Measurement of 5% weight loss temperature after curing of adhesive layer of adhesive film)", a high pressure mercury lamp was used with a wavelength of 405 nm and an illuminance of 100 mW / cm 2The accumulated light intensity is 20,000 mJ / cm 2 An adhesive film was prepared and measured in the same manner as in Example 1-1, except that the adhesive layer was cured by heating in an oven at 150° C. for 30 minutes instead of irradiating for 200 seconds so as to obtain a temperature of 100° C. The results are shown in Table 3.
[0186] The abbreviations for the resins contained in the base materials and the types of base materials shown in Table 3 are as follows. PEN: Polyethylene naphthalate PEEK: Polyetheretherketone PI: Polyimide PET: Polyethylene terephthalate PEN-containing substrate: Teonex Q83C (Teijin Ltd.) PEEK-containing substrate: EXPEEK (Kurabo Industries, Ltd.) PI-containing substrate: Upilex 25U (manufactured by UBE) PET-containing base material: LS-PET (manufactured by Toyo Cloth Co., Ltd.)
[0187] [Table 3]
[0188] (Examples 3-1 to 3-5, 3-9 to 3-11) (Preparation of adhesive film) Each material shown in Table 4 was added to 150 mL of toluene and mixed to prepare a solution containing an adhesive resin composition. Note that the bismaleimide compound 3-B in Table 4 is a bismaleimide compound represented by the above formula (10) (manufactured by Designer Molecules, "BMI-689"). The obtained solution containing the adhesive resin composition was applied to the release-treated surface of a 50 μm-thick PET film (release PET film) prepared as a separator, which had been subjected to release treatment on one side, so that the dried thickness was as shown in Table 4. The coating solution was dried by heating at 130 ° C for 10 minutes to obtain a laminated film (a) having an adhesive layer. In addition, a laminated film (b) having an adhesive layer of the thickness shown in Table 4 was produced by the same method. For a substrate of the type and thickness shown in Table 4, the laminated film (a) was laminated on one side and the laminated film (b) was laminated on the other side so that the adhesive layer faces the substrate, and the substrate was aged at 40 ° C for 24 hours to obtain an adhesive film having an adhesive layer on both sides of the substrate. In the evaluation described below, the adhesive layer derived from the laminated film (a) is referred to as adhesive layer 2 to be bonded to glass, and the adhesive layer derived from the laminated film (b) is referred to as adhesive layer 1 to be bonded to a wafer.
[0189] (Measurement of peak probe tack value after adhesive layer curing) In the same manner as in Examples 2-1 to 2-2, 2-4 to 2-6, and Comparative Examples 2-1 to 2-2, the peak probe tack value at 23° C. after curing of the adhesive layer and the peak probe tack value at 60° C. after curing of the adhesive layer were measured. The results are shown in Table 4.
[0190] (Measurement of 5% weight loss temperature after curing the adhesive layer of the adhesive film) The 5% weight loss temperature after curing of the adhesive layer of the adhesive film was measured in the same manner as in Examples 2-1 to 2-2, 2-4 to 2-6, and Comparative Examples 2-1 to 2-2. The results are shown in Table 4.
[0191] (Measurement of 10% weight loss temperature of adhesive film) Each adhesive film obtained was cut into a size of 5 mm wide x 10 mm long to prepare a test piece. The obtained test piece was weighed into an aluminum pan, and the aluminum pan was set in a differential thermal-thermogravimetric simultaneous measuring device (Hitachi High-Tech Science Corporation, "STA7200RV"), and the temperature was raised at a heating rate of 10°C / min in a temperature range from 30°C to 500°C under a nitrogen atmosphere. The temperature at which the mass of the adhesive film decreased by 10% compared to the mass before heating was taken as the 10% weight loss temperature (°C). Note that the test piece was not laminated with a release PET film to protect the adhesive layer. The results are shown in Table 4.
[0192] (Measurement of water absorption rate of adhesive film when left for one day under conditions of 23℃ and 50% RH) Each of the obtained adhesive films was cut into a size of 20 mm wide x 50 mm long to prepare a test piece, which was then dried for 1 hour under an environment of 130°C and 50% RH. The mass W 0 Furthermore, the mass W 0 After the measurement, the test piece is left to stand for one day under conditions of 23°C and 50% RH, and the mass W 1 The obtained W 0 , W 1 Using the above, the water absorption rate (%) of the adhesive film when left to stand for one day under the conditions of 23°C and 50% RH was calculated according to the following formula (I). Note that no release PET film was laminated on the test piece to protect the adhesive layer. The results are shown in Table 4. Water absorption rate (%)={(W 1 -W 0 ) / W 0}×100 (I) (W 0 W: Mass of the test piece immediately after drying for 1 hour under 130℃ and 50% RH 1 (Weight of test piece after leaving it for 1 day under the conditions of 23℃ and 50% RH)
[0193] (Measurement of ultraviolet transmittance of adhesive film at 405 nm wavelength) Each adhesive film obtained was cut to a size of 50 mm wide x 50 mm long to prepare a test piece. The ultraviolet transmittance (%) of the prepared test piece at a wavelength of 405 nm was measured using a spectrophotometer (manufactured by JASCO Corporation, "V-670"). Note that no release PET film was laminated on the test piece to protect the adhesive layer. The results are shown in Table 4.
[0194] (Measurement of tensile storage modulus at 23°C after irradiating the adhesive layer with light of 405 nm wavelength) The adhesive layer was irradiated with light having a wavelength of 405 nm and then the tensile storage modulus was measured at 23° C. in the same manner as in Examples 2-1 to 2-2, 2-4 to 2-6, and Comparative Examples 2-1 to 2-2. The results are shown in Table 4.
[0195] (Measurement of anchoring strength to substrate at 23°C after irradiating adhesive layer with light of 405 nm wavelength) In the same manner as in Examples 2-1 to 2-2, 2-4 to 2-6, and Comparative Examples 2-1 to 2-2, the adhesive layer was irradiated with light having a wavelength of 405 nm and then the anchoring strength to the substrate was measured at 23° C. The results are shown in Table 4.
[0196] (Examples 3-6 to 3-8) For the substrates shown in Table 4, a pretreatment was performed by drying for 10 minutes in an environment of 130°C and 50% RH, and then laminated with the laminate film (a) and the laminate film (b). Except for this, adhesive films were produced in the same manner as in Examples 3-1 to 3-5 and 3-9 to 3-11, and various measurements were carried out in the same manner as in Examples 3-1 to 3-5 and 3-11. The results are shown in Table 4.
[0197] The abbreviations for the resin materials and types of substrates contained in the substrates shown in Table 4 are as follows. PEEK: Polyetheretherketone PEN: Polyethylene naphthalate PET: Polyethylene terephthalate PEEK-containing substrate: EXPEEK (Kurabo Industries, Ltd.) PEN-containing substrate: Teonex Q83C (Teijin Ltd.) Polyamide-containing base material: Uniamide EX-25 (manufactured by Unitika Ltd.) Polyimide-containing substrate: Upilex 25U (manufactured by UBE) PET film: LS-PET (manufactured by Toyo Cross Co., Ltd.)
[0198] [Table 4]
[0199] <Evaluation> The adhesive films obtained in the examples and comparative examples were evaluated by the following methods. The results are shown in Tables 5 to 9.
[0200] (1) Heat resistance One of the release PET films of the obtained adhesive film was peeled off, and the film was attached to a glass (manufactured by SCHOTT, "Tempax") having a diameter of 200 mm and a thickness of 600 μm under vacuum and at a temperature of 40° C., and the adhesive film was cut into the shape of a silicon wafer. Next, the other release PET film of the attached adhesive film was peeled off, and a silicon wafer having a diameter of 200 mm and a thickness of 700 μm was attached to the surface opposite to the surface attached to the glass under vacuum and at 90° C. using a pressure lamination device (manufactured by Takatori, "GWSM-300M") to produce a laminate. A super-high pressure mercury lamp was used to illuminate the glass side of the obtained laminate with a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 The adhesive layer was cured by irradiating for 200 seconds so as to cure. The prepared laminate was heated at 250°C using a hot plate (MSA Factory, "PH224 / 225"), and the time from when heating of the laminate began to 0 seconds was measured until the adhesive film of the laminate peeled off. The heat resistance of the adhesive film was evaluated as follows: "O" if the adhesive film of the laminate did not peel off or deform even after 30 minutes, "△" if the time until the adhesive film of the laminate peeled off or deformed was 15 minutes or more but less than 30 minutes, and "X" if the time until the adhesive film of the laminate peeled off or deformed was less than 15 minutes. Moreover, for Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-2, and Examples 3-1 to 3-11, the adhesive layer 1 side was attached to a silicon wafer and the adhesive layer 2 side was attached to glass, and the evaluation was performed.
[0201] (2) Ease of use The obtained adhesive film was cut into a size of 30 cm wide x 30 cm long to prepare a test piece, and the separator protecting the adhesive layer was gently peeled off by hand from one corner of the test piece. The adhesive film was visually observed during and after the separator was peeled off, and the handleability of the adhesive film was evaluated according to the following criteria. Note that, for Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-2, and Examples 3-1 to 3-11, the separator on the adhesive layer 1 side was peeled off and the evaluation was performed. ○: The separator could be peeled off without any problems. ×: When the separator was peeled off, the adhesive layer peeled off from the substrate, or even a part of the adhesive layer was lifted off.
[0202] (3) Removability from uneven substrates (3-1) Backed Instead of a silicon wafer, a wafer with a test pattern having a PBO film on the surface (Waltz Corporation, "WALTS-TEG FBW100A-0001JY", Cu pillar height: 35 μm, SnAg height on Cu pillar: 15 μm) was used, and a laminate was produced in the same manner as in "(1) Heat resistance" above, except that an adhesive film was attached to the surface of the wafer with the Cu pillars. A super-high pressure mercury lamp was used to illuminate the glass side of the obtained laminate with a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2After the adhesive layer was cured by irradiating the laminate for 200 seconds, the laminate was heated at 250°C for 30 minutes using a hot plate (MSA Factory, "PH224 / 225"). After natural air cooling, the laminate was irradiated from the glass side with a wavelength of 355 nm and an irradiation energy density of 700 mJ / cm. 2 A pulsed laser with a frequency of 60 kHz was irradiated onto the entire glass surface to peel the glass from the adhesive film. A polyimide tape (3M, "5413", width 25 mm) was attached to the adhesive film of the laminate after the glass was peeled off, and the adhesive film was cut to the same width as the polyimide tape to prepare a backing sample for evaluating peelability. For the obtained peelability evaluation sample, the adhesive film was heated to 60°C and the peel angle was adjusted to 180° using an angle-adjustable adhesive / coating peel analysis device VPA-2S (manufactured by Kyowa Interface Science Co., Ltd.), the adhesive film was peeled off from the uneven wafer, and the 180° peel force (N / inch) was measured. The removability of the adhesive film from the uneven substrate was evaluated based on the following criteria: if the obtained 180° peel force was less than 20 N / inch, it was marked as "○", if it was 20 N / inch or more but less than 30 N / inch, it was marked as "△", and if it was 30 N / inch or more, it was marked as "X". Even if the evaluation is "x", the adhesive film of the present invention can be used without any problem depending on the application. In addition, for Comparative Examples 1-2 to 1-3 and Comparative Examples 2-1 to 2-2, the above-mentioned "(1) Heat resistance" was rated "x", and therefore this evaluation was not performed. Moreover, for Examples 2-1 to 2-6 and Examples 3-1 to 3-11, the adhesive layer 1 side was attached to a wafer with a test pattern having a PBO film on the surface, and the adhesive layer 2 side was attached to glass, and the evaluation was performed.
[0203] (3-2) No backing The removability of the adhesive film from the uneven substrate was evaluated in the same manner as in the evaluation of "(1) with backing" described above, except that the adhesive film after the glass of the laminate was peeled off was not backed with polyimide tape. Even if the evaluation is "x", the adhesive film of the present invention can be used without any problem depending on the application. Moreover, for Comparative Examples 1-2 to 1-3 and Comparative Examples 2-1 to 2-2, the above-mentioned "(heat resistance)" was rated "x", and therefore this evaluation was not performed.
[0204] In order to evaluate the heat resistance at a higher temperature, the following arbitrary evaluations (4-1) to (4-3) were performed. If the above-mentioned evaluation of "(1) heat resistance" is not "x", the adhesive film of the present invention has excellent heat resistance, so even if the evaluations of the following (4-1) to (4-3) are "x", the adhesive film can be used without problems depending on the application. If the evaluations of the following (4-1) to (4-3) are not "x", the adhesive film of the present invention has even better heat resistance.
[0205] (4-1) Heat resistance test at 260℃ The separator on one side of the adhesive film obtained in Examples 1-1 to 1-11 and Comparative Examples 1-1 to 1-5 was peeled off, and the film was manually bonded to a quartz glass having a diameter of 8 inches and a thickness of 800 μm. Furthermore, the separator on the other side of the adhesive film bonded to the quartz glass was peeled off, and a silicon bare wafer having a diameter of 8 inches was bonded to the film using a vacuum bonding device (manufactured by Takatori Corporation, "GWSM-300M") under conditions of a vacuum of 100 Pa, a temperature of 80°C, and a pressure of 0.5 MPa x 300 sec to obtain a glass wafer laminate. An ultra-high pressure mercury lamp with a wavelength of 405 nm and an illuminance of 80 mW / cm was used on the glass side of the obtained glass wafer laminate. 2 For Example 1-9 having an adhesive layer on only one side, the separator of the adhesive film was peeled off, and the adhesive film was bonded to a bare silicon wafer having a diameter of 8 inches under conditions of a vacuum of 100 Pa, a temperature of 40° C., and a pressure of 0.5 MPa for 300 sec using a vacuum bonding device (manufactured by Takatori Corporation, “GWSM-300M”), and then the adhesive film was irradiated with light having a wavelength of 405 nm and an illuminance of 80 mW / cm from the substrate side. 2 The test sample was obtained by irradiating the sample with light for 300 seconds. The prepared test sample was placed in an oven heated to 260° C. and left to stand for 30 minutes in an environment of 260° C. to carry out a heat resistance test. After the heat resistance test, the glass wafer laminate was removed from the oven, and the adhesive surfaces on both sides of the adhesive film were visually observed to confirm the ratio of the area where the adhesive film had peeled off to the entire adhesive surface (peeled area), and the heat resistance of the adhesive film at ultra-high temperatures was evaluated according to the following criteria. ◯: Peeled area was about 5% or less. Δ: The peeled area was more than 5% and less than about 30%. ×: Peeling area was about 30% or more.
[0206] (4-2) Weight loss rate of adhesive layer at 300℃ The adhesive films obtained in Examples 1-1 to 1-11 and Comparative Examples 1-1 to 1-5 were cut to a size of φ4 mm to prepare test pieces. The obtained test pieces were weighed into an aluminum pan, and the aluminum pan was set in a differential thermal-thermogravimetric simultaneous analyzer "STA7200RV (manufactured by Hitachi High-Tech Science Corporation)". The weight of the test piece when heated from 30°C to 300°C at a heating rate of 10°C / min under a nitrogen atmosphere was compared with the weight before heating to measure the weight loss rate (%) of the adhesive layer at 300°C. Note that no release PET film to protect the adhesive layer was laminated on the test piece. The heat resistance of the resulting adhesive layer was evaluated by rating it as "◯" when the weight loss rate (%) at 300° C. was 4% or less, and "×" when it was more than 4%.
[0207] (4-3) Film peeling at 300℃ The obtained adhesive film was cut into a circle with a diameter of 200 mm. Next, one release PET film was peeled off from the cut adhesive film and attached to a silicon wafer with a diameter of 200 mm and a thickness of 700 μm under vacuum and 40° C. conditions. Next, the other release PET film was peeled off, and a glass (manufactured by SCHOTT, “Tempax”) with a diameter of 200 mm and a thickness of 600 μm was attached to the surface opposite to the surface attached to the silicon wafer under vacuum and 90° C. conditions using a pressure lamination device (manufactured by Takatori, “GWSM-300M”) to obtain a laminate. The obtained laminate was heated for 30 minutes using a hot plate (manufactured by ASONE, “ND-3HA”) at 300° C. The heated laminate was observed from the glass side using a stereomicroscope and evaluated according to the following criteria. ◯: There was no change in appearance of the adhesive layer of the adhesive film and the adhesive surface between the glass and the adhesive film. Δ: There was no change in appearance of the adhesive layer of the adhesive film and the adhesive surface between the glass and the adhesive film, but the substrate was melted. ×: The adhesive layer of the adhesive film was melted, or bubbles were generated on the adhesive surface between the glass and the adhesive film. In addition, for Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-2, and Examples 3-1 to 3-11, the adhesive layer 1 side was attached to a silicon wafer and the adhesive layer 2 side was attached to glass, and the evaluations were performed.
[0208] [Table 5]
[0209] [Table 6]
[0210] [Table 7]
[0211] [Table 8]
[0212] [Table 9] [Industrial Applicability]
[0213] According to the present invention, it is possible to provide an adhesive film that can achieve both high heat resistance and excellent handleability. Also, according to the present invention, it is possible to provide a method for producing an adhesive film that can achieve both high heat resistance and excellent handleability.
Claims
1. An adhesive film having an adhesive layer and a substrate, The adhesive layer contains a photocurable adhesive, The adhesive layer was formed by irradiating the adhesive film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm. 2 the anchoring strength to the substrate at 23°C after irradiation with light of 0.10 N / 25 mm or more for 300 seconds; The adhesive layer is irradiated with a super-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 80 mW / cm 2 The tensile storage modulus at 23°C after irradiation with light of 1.0 x 10 for 300 seconds was 1.0 x 10 8 Pa or more An adhesive film characterized in that
2. An adhesive film having an adhesive layer and a substrate, The adhesive layer contains a photocurable adhesive, the adhesive film is attached to glass, and after irradiating light from the adhesive film side, the adhesive layer in contact with the glass has an anchor strength of 0.10 N / 25 mm or more at 23° C. to the substrate; The adhesive layer was attached to glass, and light was irradiated from the adhesive layer side. After that, the tensile storage modulus of the adhesive layer in contact with the glass at 23° C. was 1.0×10 8 Pa or more An adhesive film characterized in that
3. 3. The adhesive film according to claim 1, wherein at least one surface of the substrate has an easy-adhesion layer.
4. 4. The adhesive film according to claim 3, wherein the easy-adhesion layer comprises at least one layer selected from the group consisting of a corona-treated layer, a plasma-treated layer, a sandblasted layer, a chemically etched layer, and a treatment-coated layer.
5. 3. The adhesive film according to claim 1, wherein the substrate has a glass transition temperature (Tg) of 100° C. or higher.
6. 3. The adhesive film according to claim 1, wherein the substrate has a melting point of 150° C. or higher.
7. The photocurable adhesive contains a curable resin, 3. The adhesive film according to claim 1, wherein the curable resin contains a compound having an imide bond.
8. 3. The adhesive film according to claim 1, wherein the adhesive layer has a glass transition temperature (Tg) in an uncured state that is greater than 0° C. and less than 100° C.
9. The adhesive layer was formed by irradiating the adhesive film with an ultra-high pressure mercury lamp at a wavelength of 405 nm and an illuminance of 100 mW / cm. 2 The accumulated light intensity is 20,000 mJ / cm 2 After irradiating for 200 seconds so as to obtain a peak probe tack value of 0.30 N / cm at 60° C. 2 The adhesive film according to claim 1 or 2.
10. 3. The adhesive film according to claim 1, wherein the adhesive layer is provided on both sides of the substrate.
11. 3. The adhesive film according to claim 1, wherein the adhesive film has a water absorption rate of 0.60% or less when left standing for one day under conditions of 23[deg.] C. and 50% RH.
12. 3. The adhesive film according to claim 1, wherein the adhesive film has a 10% weight loss temperature of 425° C. or higher.
13. 3. The adhesive film according to claim 1, which is used for temporarily fixing electronic parts.
14. An adhesive film having an adhesive layer and a substrate, The adhesive layer contains a photocurable adhesive, The adhesive film is attached to glass, and after irradiating light from the adhesive film side, the adhesive layer that was in contact with the glass has an anchor strength to the substrate at 23° C. of 0.10 N / 25 mm or more. A method for producing an adhesive film, comprising the steps of: applying an adhesive directly to a substrate; A method for producing an adhesive film comprising the steps of:
15. The method for producing an adhesive film according to claim 14, further comprising a step of performing at least one surface treatment selected from corona treatment, plasma treatment, sandblasting, chemical etching, and application of a treatment agent on at least one surface of the substrate.
Citation Information
Patent Citations
Releasable tacky adhesive polymer
JP1993032946A
Thermally conductive adhesive tape, article and image display device
JP2015021067A
Base material for heat-resistant adhesive tape and heat-resistant adhesive tape composed of the same
JP2015052050A
Double-sided adhesive sheet
JP2015120876A